Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Quantifying nonlinear effects in the mid-infrared spectra of ultramafic mineral assemblages: Implications for rapid mineral identification and semi-quantitative analysis - Tao Han; Shenke Du; Tengfei Yu; Peng Lin; Zhenhao Xu (Minerals Engineering, 2026)

Agmatine protects against MAFLD via decreasing RBM15/IGF2BP2-mediated m6A modification of SREBP1 - Guangkui Bu; Yu Li; Guangfu Lin; Lichun Han; Deyi Chen; Xiaoping Lv (Molecular Biology Reports, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Interaction of ARA54 with androgen receptor in mediating testosterone-dependent regulation of caput epididymal GPX5 expression in mice - Dong-li Liu; Xin Gao; Yi-ying Wang; Yu-qing Lin; Si-han Yu; Zhao-jin Luan (Theriogenology, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Effects of sustained eccentric loading on concrete-encased concrete-filled steel tubular (CFST) columns - Zhi-Cheng Yang; Di Fan; Guan-Yuan Zhao; Li Zhu; Lin-Hai Han; Chen-Yu Zhang (Engineering Structures, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Non-covalent interactions between lignin and cellulase: From molecular mechanisms to precision regulation - Chengcheng Ye; Yuchen Han; Yanyi Tao; Lin Lv; Yu Long; Jianfeng Wu; Yongcan Jin; Wenjuan Wu (Bioresource Technology, 2026)

Nitrite reductases: From structure–function relationships to biocatalytic nitrite depletion and detection - Lin Yuan; Fang Wang; Han Zhang; Shu-Yu Ding; Zhong-Hua Yang (Trends in Food Science & Technology, 2026)

Salinity shapes biofilm community to promote partial nitrification and sulfamethoxazole removal in membrane-aerated biofilm reactors - Zhi-Cheng Wu; Yu-Lin Han; Chen-Wei Zheng; He-Ping Zhao (Journal of Water Process Engineering, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

Physicochemical characterization, antioxidant and antifreeze properties of Porphyra haitanensis polysaccharide fractions - Yu Liu; Yibing Wang; Lin Han; Xin Peng; Haige Wu; Jijuan Cao; Ziang Yao (Food Chemistry, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

A tetrahedral framework DNA-metformin nano-firefighter for quenching adipose chronic inflammation: Reprogramming macrophages to restore metabolic homeostasis in obesity - Zhuo Chen; Jiaqi Li; Alimire Alifu; Fenglin Jiang; Wenjing Tang; Zaowei Yang; Yuhao Liu; Bo Tian; Xi Chen; Yu Chen; Qi Han; Yunfeng Lin (Chemical Engineering Journal, 2026)

Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Exposure to a porcine appeasing pheromone in periparturient sows: Effects on behavior, health status, and reproductive performance - Shuang Liu; Liang Wang; Xu-Kai Nie; Chun-Yu Song; Ying-Han Chen; Lin Wang; Cai-Yu Lian (Applied Animal Behaviour Science, 2026)

Biogeochemical cycling and fate of PAHs in coral reef ecosystem: Associations with coral holobiont microbial functional profiles - Mei Xiong; Minwei Han; Kefu Yu; Xuejiao Lin; Xiangrong Xu (Water Research, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Behaviour of concrete-encased CFST hybrid member subjected to long-term bending moments - Chen-Yu Zhang; Guan-Yuan Zhao; Lin-Hai Han; Zhi-Cheng Yang (Engineering Structures, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Mechanochemical synthesis of nano calcium (aluminate) silicate hydrate seeds from industrial residues: A chemical engineering pathway to accelerate hydration of low-carbon cementitious systems - Weijie Du; Qizhi Lin; Zengqi Zhang; Yuchen Han; Fanghui Han; Xiaoming Liu; Yu Liu (Chemical Engineering Journal, 2026)

A synergistic piezo-photocatalytic strategy via BaTiO3 heterophase homojunctions for MRSA-infected diabetic wound therapy - Lei Qian; Han Lin; Min Wu; Zheng Fang; Jiawei Li; Yao Han; Jinxia Zhai; Peng Yu; Cairong Xiao; Chengyun Ning (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Multi-omics Analysis Reveals the Protection of a Quadruple Probiotic Mixture in Experimental Autoimmune Hepatitis - Yu Chen; Shuhui Wang; Anzhuo Chen; Zhuoying Lin; Han Wang; Wanneng Li; Jun Liu; Jia Yao; Dean Tian; Yu Lei; Mei Liu (Probiotics and Antimicrobial Proteins, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Postharvest properties and metabolomic profiling of cucumbers treated with hydrogen sulfide under low-temperature storage - Wei Han Foo; Mingmin Chen; Xue Zhao; Yu Xuan Lim; Lin Chen (Food Chemistry, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Permafrost slope failure and mitigation techniques in cold regions - Guo Ming; Yu Wenbing; Li Guo; Chen Lin; Han Fenglei (Bulletin of Engineering Geology and the Environment, 2026)

Enhanced label-free SERS detection of uremic toxins in clinical spent dialysate - Han Lee; Jiunn-Der Liao; Yi-Shan Guo; Chung-Yu Wang; Kuan-Hung Liu; Szu-Hsueh Lai; Bo-Shen Lin (Analytica Chimica Acta, 2026)

The Antiviral Activity and Underlying Mechanisms of Quercetin in Combating Largemouth Bass Virus Infection - Lin Huang; Wenyu Liao; Mingquan Peng; Jieying Yu; Mingzhu Liu; Junxiang Lai; Ermeng Yu; Ying Pan; Fei Ling; Shuyu Han; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2026)
Largemouth bass virus (LMBV), a member of the Ranavirus genus within the Iridoviridae family, is a significant pathogen causing high mortality and substantial economic losses in largemouth bass aquaculture. Therefore, developing effective antiviral agents against this viral infection is crucial for the largemouth bass aquaculture industry. Quercetin, a widely utilised flavonoid known for its therapeutic and prophylactic properties, was investigated for its antiviral efficacy against LMBV and underlying mechanisms in this study. The results demonstrated that quercetin significantly inhibited LMBV propagation in vitro and in vivo, and was effective in both prevention and treatment stages. Specifically, quercetin at 6.25 μg/mL suppressed LMBV (major capsid protein) MCP gene transcription by up to 92.09%, with the post‐infection treatment achieving 99.33% inhibition in vitro. Mechanistic studies revealed that quercetin reduces LMBV infectivity by disrupting viral internalisation and replication, while also potentiating cellular immune responses mediated by the IFN system. In vivo experiments further confirmed that quercetin treatment reduced viral transcription in the liver, spleen and kidney by 97.49%, 47.45% and 98.42%, respectively, at 48 h post‐infection and significantly enhanced the survival rate of infected juveniles. In conclusion, quercetin demonstrated potent antiviral activity against LMBV and might serve as a promising, eco‐friendly antiviral agent.

Critical assessment of synthetic microbial community strategies in vinegar brewing: from design paradigms to industrialization bottlenecks - Shiyuan Lin; Yongjian Yu; Yuanyuan Zhu; Ke Wang; Zhen Yu; Yuqin Wang; Dong Han; Xuezhi Wu; Nan Zhang; Shuaiwei Dou; Yunsong Yang (Critical Reviews in Food Science and Nutrition, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

From the neotropics to East Asia: first population of the Rio Grande cichlid (Herichthys cyanoguttatus) reported in Taiwan - Yu-Hsiang Lin; Jhao-Cian Hou; Yu-San Han; Yen-Ting Lin (Biological Invasions, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Enhancing the oral processing and swallowing performance of cod soft gels - Xiliang Yu; Yue Wang; Lin Han; Shiyi Liu; Michelle Ji Yeon Yoo; Xiuping Dong (Journal of Food Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Machine-learning-guided extraction optimization and physicochemical characteristic of GRAS microalgae proteins for sustainable food applications - Wei Han Foo; Mingmin Chen; Yu Xuan Lim; Lin Chen (Food Hydrocolloids, 2026)

Biodegradable mulch film-enriched with biochar, chicken feather, and oyster shell powder for improved soil quality and crop productivity - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Environmental Research, 2026)

Formation and evolution of sandy deserts in China: A review - Xin Wang; Ziying Yu; Han Hu; Chongwen Luo; Wenjing Yang; Jiayi Lin; Yu Cao; Zaijun Li; Fei Wang; Baofeng Li; Shengqian Chen; Huayu Lu; et al. (Earth-Science Reviews, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

An integrated strategy for Cyclotella cryptica cultivation: From antibiotic selection to efficient mixotrophic bioprocessing - Yalan Yu; Zhichao He; Tengsheng Qiao; Sizhe Fan; Lin Zhang; Jian Li; Spiros N. Agathos; Kehou Pan; Jichang Han (Algal Research, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Physical mechanism of winter temperature multi-decadal variability in arid Central Asia over the past millennium - Hao-Yu Liu; Chun-Han Jin; Jiang-Lin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Lysosomal dysfunction contributes to lead (Pb) and high-fat diet (HFD)-induced neuronal apoptosis: A link with cathepsin B - Yongke Yuan; Mengchen Liu; Mengdi Zhai; Meijia Wu; Wenhui Zhang; Yongjuan Xin; Yue Ba; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (NeuroToxicology, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

In vitro and in vivo antiviral effects of myrcene on MSRV infection in largemouth bass (Micropterus salmoides) - Zhengzhao Liu; Lin Huang; Jieying Yu; Qing Yu; Mingzhu Liu; Yanxia Gao; Xiangmou Qin; Junxiang Lai; Fei Ling; Yanlei Chang; Shuyu Han; Jia Cai; et al. (Fish & Shellfish Immunology, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Charge transfer and control mechanisms in contact-electron-activated artificial synapse - Xinke Yu; Xiongxin Luo; Gaosi Han; Yueming Zhang; Zhong Lin Wang; Laipan Zhu (Chemical Engineering Journal, 2026)

Selectively regulating and UV–visible-NIR full spectrum blocked ECD based on single molecule-multivalences & resonances strategy - Huan Ling; Shuangdui Wu; Jingxin Han; Jie Zhang; Borong Lin; Xiping Zeng; Yu Wang (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Exploration of salivary biomarkers for accurate diagnosis of anxiety, depression, and somatic symptom disorder by the integration of microfluidic chip and machine learning - Rongjie Wang; Fei Xu; Lin Wang; Xue Zhang; Miao Huang; Zhun Wei; Yan Jiang; Yunhong Zhang; Xiaoshuang Chen; Yanbo Liang; Yu Zhang; Xueqin Mao; et al. (Chemical Engineering Journal, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Effect of ivarmacitinib on swelling and tenderness in small and large joints and imaging changes in patients with moderate-to-severe RA: a post hoc analysis of a phase III clinical trial - Yuxiang Han; Meng Ding; Shaoxin Cui; Yu Tian; Yushu Yang; Xuying Liu; Lin Yang; Xiaoping Wang; Hongtao Jin; Huifang Guo; Haixue Dai; Shanshan Yin; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Asymmetric Response of a Mesoscale Eddy Dipole to Typhoon Ma-on (2011) - Xianghai Zeng; Xiayan Lin; Yu Liu; Guoqing Han; Juncheng Xie; Han Zhang (Journal of Marine Science and Engineering, 2026)
Typhoon passages typically induce significant upper-ocean responses, especially on the right side of the typhoon track. However, how mesoscale eddies modulate this left–right asymmetry remains insufficiently understood. Using high-resolution remote sensing data and reanalysis datasets, this study examines the impacts of a mesoscale eddy dipole influenced by Typhoon Ma-on (2011). The study finds that: (1) The eddy responses exhibit significant asymmetry: during Typhoon Ma-on (2011), the amplitude, circulation speed, and radius of the left side cyclonic eddy (CE) showed anomaly increases of 8.6 cm, 4.3 cm/s, and 54.3 km, respectively, whereas those of the right-side anticyclonic eddy (AE) showed anomaly decreases of 2.9 cm, 4.8 cm/s, and 13.9 km. (2) Mesoscale eddies modulate sea surface cooling with significant left–right asymmetry, differing from the conventional pattern of stronger right-side cooling. The left side CE enhanced surface cooling by up to 2.38 °C, while the right-side AE exerted a suppressing effect, with a cooling magnitude of 0.96 °C. (3) Within the CE, a significant negative temperature anomaly develops below about 20 m. Despite a relatively high Richardson number (Ri) and weak vertical shear that suppress excessive turbulent mixing, negative Ws-driven upwelling dominates, allowing cold water to be efficiently uplifted and maintaining or intensifying surface cooling. In contrast, the AE exhibits surface cooling but persistent positive anomalies below about 40 m, reflecting the partial retention of its subsurface warm water. In this case, reduced Ri and enhanced shear instability promote stronger vertical mixing, enabling subsurface heat to be transported upward, thereby offsetting and weakening the surface cooling signal.

Mariana trench-derived fungal polysaccharide AVP214–1 inhibits Singapore grouper iridovirus infection in vitro and in vivo - Xinyu Liao; Gaoqi Yu; Xiaohui Zheng; Yanqi Zhao; Siting Wu; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Zhuang Han; Qiwei Qin; Jingguang Wei (Aquaculture, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Chronology and geochemistry of radiolarian chert from Zhongba, southern Xizang (Tibet): Implications for the evolution of the Neo-Tethys Ocean - Han Yan; Han-Ting Zhong; Zong-Qi Lin; Chen-Yu Wang; Ling-Xue Gao; Cai Wang; Ming-Cai Hou (Palaeoworld, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Microbial N2O production and the functional communities regulated by groundwater flow regime - Yaqi Wang; Helin Wang; Lin Zhang; Yu Han; Ping Li; Yanxin Wang (Journal of Hydrology, 2026)

Corrigendum to “Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration”. [229 (2026) 118495/FRIN 118495] - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Robigenin in combating largemouth bass ranavirus: Investigating the antiviral potency and underlying mechanisms - Wenyu Liao; Lin Huang; Jieying Yu; Mingzhu Liu; Nijia Xue; Junxiang Lai; Ermeng Yu; Fei Ling; Shuyu Han; Ying Pan; Pengfei Li; Qing Yu (Fish & Shellfish Immunology, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

PEALD-derived ultrathin Al2O3 and MgO interphases on freestanding nitrogen-doped carbon nanofibers for robust potassium-ion battery anodes - Chih-Chieh Wang; Yi-Han Lin; Chia-Yu Chang (Chemical Engineering Journal, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Blue food proteins-derived immunomodulatory peptides: sources, preparation, identification techniques, mechanisms, and critical challenges of commercial application - Yu-Han Wu; Yan Chen; Ke-Lin Zhang; Fang-Miao Yu; Bin Wang; Qi Zeng (Food Research International, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

An oriented freezing strategy for fabricating fibrous structures of plant-based chicken analog - Yao Lin; Yu Peng; Li Shen; Qiuyu Han; Quanhong Li; Xiaojun Liao; Jing Zhao (Food Hydrocolloids, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Dual-halide solid electrolyte interphase engineering with MXene enables dense (110)-oriented Li deposition for high-performance Li metal anodes - Zongyu Mao; Shuaihe Zhang; Ye Han; Yujing Xu; Shuxin Xie; Bei Huang; Shuaihong Chen; Xintong Cai; Junyu Lin; Xiao Yu; Shaozhong Zeng; Dongju Fu; et al. (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal variations in indoor thermal environments and dynamic comfort of passengers in airport terminals during winter - Yuxin Yang; Juan Yu; Deyin Zhang; Hao Tang; Wenzhong Jiang; Libin Han; Junmin Li; Borong Lin; Yu Dong (Building and Environment, 2026)

Patterns and drivers of plant- and microbial-derived carbon in a cedar plantation chronosequence of subtropical China - Yuehan Wang; Yu Li; Chengming You; Hongwei Xu; Han Li; Lin Xu; Li Zhang; Lixia Wang; Sining Liu; Bo Tan; Yaling Yuan; Jiao Li; et al. (Plant and Soil, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A novel multimodal combining radiomics and tumor–stroma ratio (TSR) improves diagnosis of gastric cancer peritoneal metastasis - Lin Zhong; Ting Lin; Dong Hou; Hongyun Huang; Shihai Zhou; Yu Lin; Yue Yu; Liangquan Liu; Jing Luo; Fanghai Han; Lang Xie (Clinical & Experimental Metastasis, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Methyl group donor‑resolved isotopic diagnostics reveal mechanistic diversity in UV‑driven methylation of Hg(II) - Lin Yang; Kun Zhang; Maojun Yu; Shiyu Li; Deming Han; Ben Yu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Journal of Hazardous Materials, 2026)

Systematic assessment and improvement for the intelligent municipal solid waste sorter - Wei-Lung Mao; Shu-Han Huang; Hsu-Cheng Chen; Jun-Wei Zeng; Yu-Hao Lin (Journal of Cleaner Production, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Dose-dependent root phenotypic plasticity in Casuarina equisetifolia: Mechanistic insights into drought adaptation strategies for coastal sand-fixation afforestation - Chen Fang; Qinqin Lin; Can Chen; Yu Chen; Han Lin; Guoying Pan; Chuanyang Jiang; Anqiang Xie; Xia Li (Journal of Arid Environments, 2026)

Impact of algal blooms on phosphorus migration: Insights from laboratory and field cultivation enrichment experiments in the yangtze river estuary - Yu-Yuan Wang; Zhi-Li Guo; Han-Lin Jiang; Yuan-Zhe Ni; Li-Min Zhou; Gui-Peng Yang; Xiao-Yan Cao (Estuarine, Coastal and Shelf Science, 2026)

Design and synthesis of multifunctional polyaspartic acid derivatives as green water treatment agents: Calcium scale inhibition, antibacterial activity, and fluorescence properties - Ying Zhang; Lin-Lin Zhao; Yu Han; Yu-Xia Wang; Zhong-Yan Cao; Ya-Min Cheng; Ying Xu (Desalination, 2026)

An accelerated meshfree computational framework with machine learning classification for multi-phase modeling of landslide - Kuan-Chung Lin; Yih-Chin Tai; Po-Han Lee; Hock-Kiet Wong; Yanran Wang; Yu-Shu Lu; Jiun-Shyan Chen (Computers and Geotechnics, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Highly linear bionic strain decoupling sensor mediated by curved surface stress - Xueping Zhang; Junqiu Zhang; Jiachao Wu; Yu Chen; Xueyang Li; Wenjie Yu; Xiancun Meng; Guilin Li; Lina Ju; Bo Li; Tao Sun; Zhiwu Han; et al. (Chemical Engineering Journal, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Morphological and molecular evidence reveal the Sarotherodon melanotheron invasion off Taiwan, East Asia - Yen-Ting Lin; Yu-Hsiang Lin; You-Wei Shiu; Yu-San Han (Marine Pollution Bulletin, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Comparison of metabolomic and transcriptomic analyses of Ganping mandarin fruit following on tree storage and postharvest low temperature storage - Xinyu Huang; Luoao Lin; John B. Golding; Penta Pristijono; Su Guo; Youjian Yu; Gang Chen; Dongdao Han; Huqing Yang; Ruihua Bai; Yongxin Li (Postharvest Biology and Technology, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

Continuous positive airway pressure on left ventricular ejection fraction in obstructive sleep apnea and heart failure with reduced ejection fraction: a systematic review and meta-analysis - Chou-Han Lin; Yen-Wen Wu; Chih-Chieh Yu (Sleep and Biological Rhythms, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

An aptamer integrated electrochemistry and photoluminescence dual-mode microfluidic biosensor for sensitive and accurate ovarian cancer extracellular vesicles detection - Xiaoshuang Chen; Junxia Han; Mingyuan Sun; Zhenhua Wang; Shuai Wang; Lin Han; Yu Zhang (Analytica Chimica Acta, 2026)

Cyclic responses of typical seabed materials in two offshore wind farms of China - Bo Han; Xinran Yu; Zhishuai Zhang; Genqiang Peng; Mingbao Lin; Song Dai (Marine Georesources & Geotechnology, 2025)

Integrated physiological and metabolomic analysis reveals metabolite diversity and cultivar-specific characteristics during post-ripening in four Torreya grandis cultivars - Zhenmin Ma; Han Tao; Lin Li; Ruqi Meng; Jinwei Suo; Weiwu Yu; Yuanyuan Hu; Fei Gao; Mohamed A. Farag; Zuying Zhang; Jiasheng Wu; Lili Song (Postharvest Biology and Technology, 2025)

Grain size and geochemical evidence for the integration of the Yellow River through the Sanmen Gorge - Han Hu; Ziying Yu; Jiaxing Yang; Jiayi Lin; Wenjing Yang; Baofeng Li; Gang Hu; Xin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Biocontrol potential and cryopreservation of marine ciliates for sustainable management of bacterial pathogens in aquaculture - Xin-Long Liu; Sin-Wei Lin; Wei-Yu Yeh; Hung-Yun Lin; Han-Jia Lin (Fish & Shellfish Immunology, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Mitochondrial pyruvate carrier proteins mediate host-pathogen interactions during WSSV infection in shrimp - Yu-Chen Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

A sequential nanotherapy potentiate anti-angiogenic therapy by disrupting lipid metabolism under metabolic stress - Qiye Xi; Xiaojing Lin; Yixian Xie; Fengyong Cheng; Ben Hu; Fengling Zhang; Fushan Sun; Bing Han; Yufang Lai; Yongxia Wang; Jigang Wang; Meng Yu (Chemical Engineering Journal, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Rice straw–derived biochar-enriched biodegradable mulch film for enhancing soil organic carbon - Kesinee Iamsaard; Girma Sisay Wolde; Chih-Huang Weng; Han-Yu Hsueh; Jenn-Wen Huang; Yao-Tung Lin (Bioresource Technology Reports, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Revision of the Armoreye dory genus Zenion (Zeiformes: Zeniontidae) in the South China Sea, with a description of a new species - Yen‐Ting Lin; Chia‐Hao Chang; Yu‐San Han; Chien‐Hsiang Lin (Journal of Fish Biology, 2025)
This study describes a new species of armoreye dory, Zenion boops sp. nov., from Dongsha Island, Taiwan, as part of a comprehensive revision of the genus Zenion in the South China Sea. The new species is clearly distinguishable from its tropical congeners, Z. hololepis and Z. japonicum , based on a combination of distinct morphological features, meristic counts, otolith morphology and c oxidase subunit I ( COI ) gene sequences. Z. boops is characterized by a smooth second dorsal spine, a long first dorsal spine, 30–35% of second (longest) dorsal spine, a small and narrow notch at the symphysis of the maxilla, and a relatively large eye diameter, 55–61% of head length. Furthermore, otolith morphology and phylogenetic analyses based on partial sequences of the cytochrome COI gene reveal significant genetic divergence between this new species and its congeners. With the addition of Z. boops , the genus Zenion now includes four valid species. We also present an identification key for all Zenion species and provide detailed descriptions of their otoliths. Also, we provide data that show that Z . hololepis is restricted to the Atlantic Ocean.

Influence of Human Activity on Wet Deposition and Nitrogen Species in Coastal and Marine Environments - Hung-Yu Chen; Jia-Han Lin; FuJung Tsai (Journal of Marine Science and Engineering, 2025)
In this study, 101 and 102 rainwater samples were collected from April 2020 to February 2024 in a coastal and marine area, respectively. The results show that the Cl/Na ratios in both study areas were lower than the seawater value (1.17), suggesting chloride depletion. The chloride depletion rates in both areas decreased after the COVID-19 lockdown period. The molar ratio of NH4+ to non-sea-salt sulfate (nss-SO42−) was 1.54, with a mixture of (NH4)2SO4 and NH4HSO4 in the coastal area, and 0.83, with NH4HSO4 as the main form, in the marine area. A decreasing trend attributed to high O3 and relative humidity (RH) levels occurred in 2022. Among the dissolved organic nitrogen (DON) species, DON accounted for 24% and 32% of the total dissolved nitrogen (TDN) in the coastal and marine areas, respectively, indicating a greater relative contribution under lower anthropogenic influence. On the basis of the correlation between the species and source analysis results, NO3− mainly originated from fossil fuel combustion, NH4+ originated from agricultural emissions and secondary aerosols, and DON originated from secondary aerosols via combustion processes and natural emissions. In terms of the flux, due to lockdown activities, the Dissolved Inorganic Nitrogen (DIN) flux decreased significantly from 40.6 to 19.3 mmol m−2 yr−1 in the coastal area and from 27.7 to 15.1 mmol m−2 yr−1 in the marine area. Additionally, a slight decrease occurred in the DON flux, from 21.6 to 19.3 mmol m−2 yr−1 and from 27.7 to 15.1 mmol m−2 yr−1, respectively. Regarding new production, based on nitrogen input, the level in the coastal area decreased from 5.83 to 2.10 g C m−2 yr−1, and that in the marine area decreased from 3.92 to 1.55 g C m−2 yr−1, indicating a significant reduction during the COVID-19 lockdown.

Effects of aeration gradient on simultaneous nitrification and denitrification in MABR under low nutrient concentrations: Experimental and modeling investigation - Gong-Hao Zhao; Yu-Lin Han; Chun-Yu Lai; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Application of a thiophene-based conjugated polymer in the photocatalytic eradication of multidrug-resistant bacteria: Synergistic inactivation of MRSA via carboxyl capture and multi-pathway regulation - Ying Xu; Simiao Wang; Xinyu Yu; Yuncong Wang; Lin Han; Yu Wang; Haiyong Guo; Juan Du (Journal of Hazardous Materials, 2025)

Mechanical and acoustic emission characteristics of anisotropic rock subjected to tiered cyclic intermediate principal stress - Kaihui Li; Guangzhen Du; Dongya Han; Zhen-Yu Yin; Jiangteng Li; Hang Lin (Engineering Geology, 2025)

Influence of prolonged exposure to acetamiprid on the toxicology of the decapod crustacean Pacific white shrimp Penaeus vannamei - Zhen-Fei Li; Zhi Luo; Zhi-Yu Lin; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Redefining cyclodextrin-based systems: A multiscale framework of structure, function and application interconnection - Yu-han Zhang; Yuting Lin; Yihan Lin; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Atmospheric nitrogen deposition to cropland in Fujian province, China - Ziyin Yu; Mengjuan Han; Zhang Wen; Wenqing Li; Changzheng Wu; Xin Ma; Wen Xu; Ruotong Si; Xiaoping Xia; Aohan Tang; Lin Zhang; Goulding Keith; et al. (Atmospheric Environment, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

The nexus of digital economy and regional green innovation: the moderating roles of formal and informal institutions - Yuming Zhai; Ning Xie; Han Lin; Linguo Ji; Mingchuan Yu (Environment, Development and Sustainability, 2025)

How can the deposit return scheme promote the high-value recycling of food contact PET? - Wanying Lin; Xingmin Chen; Jinfen Huo; Yuan Chen; Han Yu; Yan Lin (Environment, Development and Sustainability, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

A novel hydrogel electrolyte for self-powered sensing and safe energy storage systems in extreme environments - Wen Jiang; Yang Tao; Qiuxiang Yang; Yudong Wang; Lin Peng; Ce Zhang; Shounian Cheng; Jiandan Liang; Yu Han; Xia Cao (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Fine root trait dynamics and their relationships with productivity across grasslands under extreme drought - Yuan Shi; Taofeek O. Muraina; Saheed O. Jimoh; Niwu Te; Lin Song; Jiaqi Chen; Hongqiang Wang; Qiang Yu; Xiaoan Zuo; Xingguo Han; Wentao Luo; Scott L. Collins (Oecologia, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Olfactory dysfunction induced by pesticides: Adverse outcomes, emerging mechanisms, and risk for neurodegenerative diseases - Lin Wang; Si-Yang Liu; Han-Yue Zheng; Shou-Min Fang; Li Zhuo; Feng Xu; Quan-You Yu (Pesticide Biochemistry and Physiology, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Constructing a synthetic microbial community by analyzing the microorganisms responsible for the core flavor substances of Zhenjiang aromatic vinegar and their interaction - Yongjian Yu; Jiaxin Liu; Yuanyuan Zhu; Ke Wang; Yuqin Wang; Dong Han; Zhen Yu; Siyuan Cheng; Nan Zhang; Shuaiwei Dou; Shiyuan Lin; Ziyi Kang (Food Bioscience, 2025)

The role of eddy merging in maintaining the quasi-permanent Ulleung Eddy - Guoqing Han; Wang Zhu; Yaofeng Wang; Xiayan Lin; Juncheng Xie; Yu Liu (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Alleviating moxifloxacin-induced biological inhibition in ethanol and Cl− coexisted wastewater: Why UV/H2O2 is better than Fenton - Yingying Zhang; Min Yang; Wenbo Cui; Lin-Ji Xu; Depeng Zhang; Yu Tao; Jing-Long Han; Aijie Wang (Chemical Engineering Journal, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Effects of lichen symbiotic bacteria-derived indole-3-acetic acid on the stress responses of an algal–fungal symbiont - Yan-Yu Lin; Han-Chen Ho; Jui-Yu Chou (Brazilian Journal of Microbiology, 2025)

First and northernmost record of the invasive redhead cichlid (Vieja melanurus) in East Asia: evidence from Taipei City, Northern Taiwan - Yen-Ting Lin; Yu-Hsiang Lin; Jhao-Cian Hou; Hong-Yu Yang; Yu-San Han (Biological Invasions, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Quantifying assembly processes of dissolved organic matter pools in eutrophication using high-resolution mass spectrometry and ecological models - Guan-Lin Chen; Chen Qian; Meng Du; Min-Jie Tong; Jie-Jie Chen; Han-Qing Yu (Water Research, 2025)

Four typical variation patterns of mid-infrared spectra of the mafic mineral anomalies for fault zone identification - Zhenhao XU; Tao HAN; Tengfei YU; Peng LIN (Tunnelling and Underground Space Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Ecological risks under combined pollution: Toxicological effects of clothianidin and microplastics on Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Aquatic Toxicology, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Characteristics, immobilization of linoleic acid isomerase from Bifidobacterium breve and its application in rice bran oil - Lin Li; Ning Wang; Liqi Wang; Fuming Yang; Weining Wang; Yike Han; Dianyu Yu (Food Research International, 2025)

Potentially texture-modified food for dysphagia: Impact of Polygonatum sibiricum polysaccharide addition on gelling properties, microstructure and digestibility of bovine tendon collagen-cassava starch composite gels - Yuhong Lin; Zhuo Wang; Chaoxue Shi; Ling Han; Qunli Yu (Food Hydrocolloids, 2025)

Antiviral activity of epicatechin against Singapore grouper iridovirus in vitro and in vivo - Lin Huang; Jihui Kuang; Jieying Yu; Qing Yu; Weiqiang Xu; Mingzhu Liu; Yunyi Wei; Shuyu Han; Yanhua Huang; Pengfei Li (Fish & Shellfish Immunology, 2025)

Performance of recycled aggregate concrete-filled high-strength steel tubular members under combined compression-bending-torsion - Zhi-Cheng Yang; Lin-Hai Han; Hua-Yang Zhao; Xiang-Yu Zhou (Engineering Structures, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Reconstructed vanadium carbide MXene supported cerium based trimetallic phosphide as an efficient electrocatalyst for alkaline water splitting - Yu-Han Pan; Sakthivel Perumal; Mani Sakthivel; Shan-Ni Lin; Min-Hsin Yeh; Wen-Yueh Yu; Kuo-Chuan Ho (Chemical Engineering Journal, 2025)

Building with nature: Morphological spatial pattern of green infrastructure in urban heat mitigation - Bau-Show Lin; Yu-Hua Tsai; Han-Chin Chang; Chin-Chung Yu; Cheng-I Hsieh (Building and Environment, 2025)

Cycleift: A deep transfer learning model based on informer with cycle fine-tuning for water quality prediction - Yang Yu; Shixin Zhao; Lintong Han; Lin Peng; Yanmei Xu; Qiujin Tian; Sen Chen; Zuogang Yang; Qiude Li; Zuquan Hu (Stochastic Environmental Research and Risk Assessment, 2025)

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Transformation of iron-bearing minerals and iron resource cycling - Xianji Yu; Wenchao Zhang; Han Wang; Xingyao Ye; Zhang Lin (Resources, Conservation and Recycling, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Upcycling electroplating sludge into nanoflower-structured Cu-MOFs for efficient Fenton-like degradation of organic dyes - Jia-Yin Lin; Si-Han Yu; Jun-Ren Shih; Tsai-Hsuan Hsieh; Chih-Ying Wang; Jen-Yu Huang; Nai-Wen Tsao (Journal of Water Process Engineering, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

Pilot-scale application on Fe-C coupled natural zeolite for total nitrogen removal in low C/N black odorous water - Hongyang Yu; Qiheng Han; Tao Li; Shanshan Lin (Journal of Environmental Chemical Engineering, 2025)

Freestanding vanadium oxides/carbon hybrid cathode with long-term cyclability at low current density for flexible aqueous zinc ion batteries - Zhouyang Qin; Gaoxu Han; Yilin Yang; Shengle Hao; Lingxiao Yu; Yuxiao Lin; Yunsong Li; Ruitao Lv; Wanci Shen; Feiyu Kang; Zheng-Hong Huang (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Observer-based robust preview control for tracking low Earth orbit targets of a 2.5-meter optical telescope with wind disturbance - Jueqi Lin; Weirui Chen; Zheng Wang; Xiaojun Zhou; Yu Han (Advances in Space Research, 2025)

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

eDNA Metabarcoding Reveals the Depth-Structured Variation of Coral Reef Fish - Jinfa Zhao; Lin Lin; Yong Liu; Teng Wang; Yu Liu; Yayuan Xiao; Jianzhong Shen; Hongyu Xie; Hai Huang; Qiuying Han (Fishes, 2025)
Global coral reef ecosystems face various levels of disturbance pressure. Understanding the depth-structured variation in coral reef fish communities can help us to better grasp and predict the adaptive changes of the ecosystem under different stressors. This study applied eDNA metabarcoding technology to analyze the spatial distribution of the coral reef fish at various depths (0 m, 5 m, 10 m, 15 m, 20 m, 30 m, 40 m, 50 m, and 60 m) within the Xisha Islands of China. The results indicated that the eDNA technology detected a total of 213 amplicon sequence variants (ASVs), including 33 species that were not identified using traditional methods. Herbivorous fish generally dominated in relative abundance across different depths. Moreover, the similarity among depth groups was largely absent, and significant differences existed in fish assemblages across depth gradients, consistent with the unique depth preferences of fish microhabitats. Importantly, our findings revealed distinct depth-structured variation among different functional groups of coral reef fish. Large carnivorous fish initially increased and then decreased along the depth gradient from 0 to 60 m, with a turning point around 20 m, while large herbivorous fish displayed the opposite trend. Small carnivorous and small herbivorous fish consistently declined along the same depth gradient. Additionally, the Margalef index (D) and Function richness (FRic) both displayed a consistent downward trend with increasing depth, while the Shannon–Wiener index (H′), Pielou index (J′), Quadratic entropy (RaoQ), Functional dispersion (FDis), and Functional evenness (FEve) initially increased and then decreased, peaking around 20 m. This study revealed that eDNA metabarcoding is an effective tool for evaluating coral reef fish biodiversity, community composition, and spatial distribution. It enhances our understanding of distribution dynamics and offers valuable insights for coral reef conservation and restoration efforts.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

RAPID LEAF FALLING 1 facilitates chemical defoliation and mechanical harvesting in cotton - Bing Zhang; Dandan Yue; Bei Han; Danfan Bao; Xiao Zhang; Xuyang Hao; Xin Lin; Keith Lindsey; Longfu Zhu; Shuangxia Jin; Maojun Wang; Haijiang Xu; et al. (Molecular Plant, 2025)

Newly isolated bacterium and arbuscular mycorrhizal fungus effectively reduce the root cadmium concentration and increase the root biomass of Ophiopogon japonicus - Lin Lin; Jin Li; Obey Kudakwashe Zveushe; Ying Han; Hengxing Zhang; Yu Qin; Victor Resco de Dios; Lei Zhou; Xiangyu Xi; Wei Zhang; Yulian Zhao; Amal Mohamed Omer; et al. (Journal of Hazardous Materials, 2025)

Polystyrene microplastics attenuated the impact of perfluorobutanoic acid on Chlorella sorokiniana: Hetero-aggregation, bioavailability, physiology, and transcriptomics - Zhilin Zhao; Xiaoying Zheng; Yue Li; Zongshuo Han; Yu Tang; Tianxing Hu; Tao Lin (Journal of Hazardous Materials, 2025)

Probabilistic multi-hazard risk assessment of high-rise buildings subjected to concurrent earthquakes and strong winds - Qian-Qian Yu; Ling-Han Liu; Xiang-Lin Gu; Yao-Yao Zhang (Engineering Structures, 2025)

Seismic performance of grouted CFDST column base: Investigation and design method - Zhi-Cheng Yang; Wei Li; Yu-Feng Cheng; Lin-Hai Han (Engineering Structures, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Chemical looping of catalytic methane decomposition with reverse Boudouard reaction using dual functional Ni-FeOx nanoparticle cluster for CO2-negative H2 production - Chien-Wei Wu; Zhi Xuan Law; Yu-Chun Zeng; Kun-Han Lin; De-Hao Tsai (Chemical Engineering Journal, 2025)

Electrostatic-Induced Crystal-Rearrangement of Benzoquinones Cathode for Large-Scale All-Organic Aqueous Proton Batteries - Jianyong Zhang; Jingyuan Yu; Wenwei Zhang; Ahmed Eissa Abdelmaoula; Chunhua Han; Zhenzhen Dou; Feng Liang; Lin Xu (Chemical Engineering Journal, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Spatially explicit land use of manufacturing sectors and its biodiversity impacts in China - Yutao Wang; Zhixiu Han; Yiru Song; Chen Sun; Lin Sun; Huajun Yu (Resources, Conservation and Recycling, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Allopatric Speciation and Interspecific Gene Flow Driven by Niche Conservatism of Diploderma Tree Lizards in Taiwan - Tzong‐Han Lin; Zong‐Yu Shen; Ming‐Hsun Chou; Pei‐Wei Sun; Chin‐Chia Shen; Jen‐Pan Huang; Si‐Min Lin (Molecular Ecology, 2025)
Allopatric speciation is a widely accepted hypothesis for species distributed across geographic barriers. Meanwhile, niche conservatism, the tendency of species to retain their ancestral ecological traits, helps reinforce genetic differentiation by stabilising species distributions over time and reducing the role of competition in shaping range boundaries. In contrast, hybridisation can occur at the edges of distribution after secondary contact following climatic or geological events, leading to a reduction in genetic divergence between divergent lineages. In this study, we investigated the role of geographic barriers, niche conservatism and gene flow in the speciation history of Diploderma species in Taiwan, where geographically distinct taxa share similar environmental preferences. By using ddRAD‐seq data, seven distinct genetic clusters were identified with two putatively new cryptic species in D. brevipes and D. polygonatum . Most sister species pairs share similar climatic niches based on niche equivalency and similarity tests. We further detected significant historical gene flow between lineages of D. brevipes and D. polygonatum , where secondary contact might have occurred because of palaeoclimate changes and historical demographic expansion. Our results demonstrate that niche conservatism does not always act in concert to strengthen the result of allopatric speciation; instead, it may also lead to gene flow between divergent lineages following secondary contact. On the other hand, postdivergence gene flow may be a creating force generating phenotypic diversity in sexually selected traits in our study system. The underestimated species diversity of Diploderma in Taiwan requires further taxonomic work in the future.

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Machine Learning-Based Partition Method for Cyclic Development Mode of Submarine Soil Martials from Offshore Wind Farms - Ben He; Mingbao Lin; Zhishuai Zhang; Bo Han; Xinran Yu (Journal of Marine Science and Engineering, 2025)
Offshore wind turbines are subjected to long-term cyclic loads, and the seabed materials surrounding the foundation are susceptible to failure, which affects the safe construction and normal operation of offshore wind turbines. The existing studies of the cyclic mechanical properties of submarine soils focus on the accumulation strain and liquefaction, and few targeted studies are conducted on the hysteresis loop under cyclic loads. Therefore, 78 representative submarine soil samples from four offshore wind farms are tested in the study, and the cyclic behaviors under different confining pressures and CSR are investigated. The experiments reveal two unique development modes and specify the critical CSR of five submarine soil martials under different testing conductions. Based on the dynamic triaxial test results, the machine learning-based partition models for cyclic development mode were established, and the discrimination accuracy of the hysteresis loop were discussed. This study found that the RF model has a better generalization ability and higher accuracy than the GBDT model in discriminating the hysteresis loop of submarine soil, the RF model has achieved a prediction accuracy of 0.96 and a recall of 0.95 on the test dataset, which provides an important theoretical basis and technical support for the design and construction of offshore wind turbines.

From the Atlantic-Mediterranean to the Western Pacific: First record of potentially harmful invasive gilthead sea bream (Sparus aurata) in the Northern Taiwan - Yen-Ting Lin; Yu-San Han (Marine Pollution Bulletin, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Surgical treatment of Meniere’s disease - Yixu Wang; Hongwei Zheng; Xin Ma; Lin Han; Tongxiang Diao; Lisheng Yu; Maoli Duan (Science Bulletin, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Chronological and palaeoecological insights into the Dayakou fauna in Yanjinggou, Chongqing, China: Responses of large mammals to the Early-Middle Pleistocene Climate Transition - Haiqian Hu; Haowen Tong; Fei Han; Hui Dai; Wanbo Huang; Qigao Jiangzuo; Paul Rummy; Xunqian Wang; Yu Lin; Guangbiao Wei (Quaternary Science Reviews, 2025)

Co-adsorption of methylene blue/Pb(II) from aqueous solutions using sulfonated mesoporous diatomite - Ali M. Abou-Elanwar; So Young Lee; Jeongkyun Yu; Jieun Kim; Chihyun Hwang; Hyungmin Park; Young-tai Noh; Ming Xie; Jiuyang Lin; Seong-Ju Park; Dong Han Seo; Youngjin Kim (Journal of Water Process Engineering, 2025)

Analyzing the influence of pore structure and vibration on clogging in pervious concrete - Wuguang Lin; Lin Liu; Han Ye; Qifeng Yu; Yoon-Ho Cho (Journal of Cleaner Production, 2025)

Atmospheric black carbon (BC) in Hangzhou, China: Temporal variation, source apportionment, and case study of the 19th Asian Games - Jian Lin; Deming Han; Feng Chen; Xiaorong Zhang; Yang Yang; Lin Yang; Hua Guo; Zechen Yu; Liuyan Cao; Jianbo Shi; Guibin Jiang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Combined exposure effects: Multilevel impact analysis of cycloxaprid and microplastics on Penaeus vannamei - Zhi-Yu Lin; Zhi Luo; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Monotonic and cyclic mechanical characteristics of reconstituted soil with high liquid limit reinforced by steel slag - Cheng-Shuang Yin; Han-Lin Wang; Xiao-Ming Liu; Xiao-Qing Yu; Xin Kang; Askar Khasanov (Bulletin of Engineering Geology and the Environment, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Biological activities of benzofurans from the fruits of Psoralea corylifolia L. and their mechanism based on network pharmacology and biological verification - Peixin Shi; Xiaohui Yu; Min Zhang; Lin Wang; Linkui Deng; Jun Yin; Na Han (Phytochemistry, 2025)

Integration of manganese ores with activated carbon into constructed wetland for greenhouse gas emissions reduction - Yu Huang; Xiaoying Zheng; Zhilin Zhao; Jiaqing Tao; Tianxing Hu; Zongshuo Han; Tao Lin (Journal of Environmental Management, 2025)

Efficient photoelectrocatalytic degradation of tetracycline coupled with hydrogen production by N-doped carbon layer-wrapped TiO2 nanorods - Yan Li; Lili Yu; Jiayang Xie; Zilong Han; Haotong Chen; Zhiyuan Zhang; Zehao Lin; Li Li (Journal of Environmental Chemical Engineering, 2025)

Half-day (daytime and nighttime) precipitation extremes in China: Changes and attribution from 1981 to 2022 - Jiahao Han; Shibo Fang; Xiaomao Lin; Zhanhao Zhang; Man Li; Yanru Yu; Wen Zhuo; Xinyu Wang (Global and Planetary Change, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

MEHP induced mitochondrial damage by promoting ROS production in CIK cells, leading to apoptosis, autophagy, cell cycle arrest - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

A simple and efficient TALEN system for genome editing in plants - Qing Liu; Lizhou Lin; Shengjian He; Jianghui Yu; Caili Xie; Chaoyue Gai; Yongqiang Han; Chunmei Liu; Feihan Huang; Daoqian Chen; Yuanyuan Song; Guannan Qin; et al. (Plant Molecular Biology, 2025)

Characteristics of Tylvalosin Tartrate Enteric Amorphous Pellets Prepared by Liquid Layering - Haoran Wang; Lin Han; Han Zeng; Mengyao Yu; Tian Yin; Yu Zhang; Haibing He; Jingxin Gou; Xing Tang (Pharmaceutical Research, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Integrated transcriptomic and proteomic analysis unravels the response mechanisms of Saccharina japonica to heat stress - Zhongyuan Lin; Xuelian Liu; Jinbin Lin; Feng Lin; Yijuan Han; Huibin Xu; Hongmei Lin; Weiqi Tang; Yu Qin; Yanbing Zhu; Hui Ni; Jianjun Lu; et al. (Aquaculture, 2025)

A bottom-up nationwide analysis of sectoral land use reveals spatial heterogeneity across the United States - Zhixiu Han; Wei Xie; Yiru Song; Lin Sun; Huajun Yu; Bin Chen; Yang Li; Yutao Wang (Resources, Conservation and Recycling, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Occurrence characteristics, removal efficiencies and potential health risks of typical viruses in rural domestic sewage: A review - Yingming Zhu; Su Xu; Yu Zhou; Xuesong Guo; Yunping Han; Jun Zhan; Lin Li; Junxin Liu (Journal of Water Process Engineering, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Comparative analyses of bacterial contamination and microbiome of broiler carcasses in wet market and industrial processing environments - Yuanyuan Zhou; Nan-lin Wang; Jin-qi Cen; Jia-tong Han; Yu-xuan Tang; Zi-qi Xu; Hang Zeng; Kurt Houf; Zhongjia Yu (International Journal of Food Microbiology, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Synergistic effects of accompanying heterotrophic bacteria on sulfide-based autotrophic denitrification - Yu-Lin Han; Zhen-Chuan Wu; Feng Jiang; He-Ping Zhao (Chemical Engineering Journal, 2025)

Triboelectric materials with UV protection, anti-bacterial activity, and green closed-loop recycling for medical monitoring - Jiandan Liang; Qiuxiang Yang; Ce Zhang; Wen Jiang; Shounian Cheng; Yang Tao; Lin Peng; Yu Han; Xia Cao; Zhong Lin Wang (Chemical Engineering Journal, 2025)

Achieving efficient autotrophic nitrogen removal in anaerobic membrane bioreactor plus membrane aerated biofilm reactor by regulating nutrient ratios - Yu-Lin Han; Ling-Dong Shi; He-Ping Zhao (Bioresource Technology, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

A high selective separation method for high-purity polysaccharides from dandelions by density-oriented deep eutectic solvent ultrasonic-assisted system - Han Zhang; Yu Lin; Yanan Bao; Wen-Jing Li; Bo Hong; Min Zhao (Sustainable Chemistry and Pharmacy, 2024)

Perfluorobutanoic acid weakens the heterogeneous aggregation of microplastics and microalgae: Perspective from physicochemical properties, extracellular polymeric substances secretion and DLVO theory - Yue Li; Xiaoying Zheng; Zhilin Zhao; Wenfei Li; Yu Huang; Haidong He; Zongshuo Han; Jiaqing Tao; Tao Lin (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Failure criterion of submarine completely weathered granite under cyclic loads in rock-based sea area - Song Dai; Xinran Yu; Bo Han; Zhishuang Zhang; Ben He; Mingbao Lin (Ocean Engineering, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Enhancement of the reactivation process of long-term starved anammox granular sludge with gravel balls: Microbial succession and metabolic impact - Xinlong Wang; Qiheng Han; Hongyang Yu; Shanshan Lin (Environmental Research, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Improved identification and tracking of three-dimensional eddies in the Southern Ocean utilizing 3D-U-Res-Net - Chang Liu; Xiayan Lin; Guangjun Xu; Guoqing Han; Yu Liu (Frontiers in Marine Science, 2024)
Oceanic mesoscale eddies are prevalent throughout the global ocean, playing a critical role in material and energy transport while significantly influencing climate change. Accurate characterization of their three-dimensional structures and movement is essential for a quantitative analysis of their transport processes. Traditional eddy detection algorithms have lower successful detection rate and with more limitations, so they fall short in the complex and dynamic ocean environment. The rising trend of applying artificial intelligence (AI) algorithms, due to their efficiency, precision, and automation, addresses this challenge. This study employs the 3D-U-Res-Net algorithm to identify the three-dimensional structures of mesoscale eddies in the Southern Ocean using GLORYS12V1 data from 2011 to 2020. A vector geometry-based eddy detection algorithm (VG) initially identified 1587292 eddy snapshots in the Southern Ocean (2011–2019), which were used for training the 3D-U-Res-Net algorithm. Data from 2020 served as the ground truth and validation set. The successful detection rate of 3D-U-Res-Net algorithm is 100%, which means that it identified all 135734 eddy snapshots from the VG dataset in 2020. For eddy tracking, the VG algorithm counted 18168 eddy tracks, whereas the 3D-U-Res-Net counted 18559, reflecting a 2.15% bias. To reduce uncertainty, eddies with lifespans shorter than two weeks were excluded. The average lifespans and traveling distances for eddies detected by the 3D-U-Res-Net (VG) algorithm were 29.35 (29.61) days and 77.78 (37.60) km, respectively, with the 3D-U-Res-Net identifying eddies with longer traveling distances. The mean radius of eddies detected by the VG algorithm was 43.16 km, while the 3D-U-Res-Net detected eddies with a mean radius of 43.74 km, a 0.58 km increase. We categorized eddies into four three-dimensional structures: bowl-shaped, cone-shaped, lens-shaped, and cylindrical. The VG algorithm identified these structures in proportions of 32%, 31%, 25%, and 12%, respectively, whereas the 3D-U-Res-Net algorithm found 19.48%, 19.58%, 0.04%, and 60.9%, respectively. The 3D-U-Res-Net identified more cylindrical eddies and was approximately ten times faster than the VG algorithm. Overall, this algorithm has good performance and higher efficiency. It is an attempt of using AI for oceanic research, and more works can be carried out in the future.

Comprehensive evaluation of the nephrotoxicity of carbon quantum dots: Effects of the surface charge - Pei-Luen Jiang; Yan-Yu Hong; Lingyan Yang; Han-Jia Lin; Chih-Ching Huang; Yan-Hua Chen; Chia-Hua Lin; Yi-Chun Chen (Chemosphere, 2024)

Decomposing high uncertainty in greenhouse gas mitigation pathways in emerging regions: An approach to evaluate risks toward carbon neutrality - Hui Han; Xinxin Ye; Yahui Bian; Shuifa Lin; Yu-Sheng Shen; Zhi Huang; Jianyi Lin (Science of The Total Environment, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Urban green vitalization and its impact on green exposure equity: A case study of Shanghai city, China - Hongkai Geng; Tao Lin; Ji Han; Yicheng Zheng; Junmao Zhang; Zixu Jia; Yuan Chen; Meixia Lin; Long Yu; Yukui Zhang (Journal of Environmental Management, 2024)

Surface S doping induced ladder-regulation of lattice oxygen on the vertical FeCoOOH for water oxidation - Ning Yu; Ren-Ni Luan; Chao-Yue Gu; Yi-Lin Dong; Guanqun Han; Han Hu; Bin Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

Warming mitigates the effects of nitrogen addition on the soil diazotrophic community in a subtropical forest - Jiling Cao; Lin Li; Yu Han; Zhiyuan Liu; Faying Lai; Yusheng Yang (Applied Soil Ecology, 2024)

The impact of social partners: investigating mixed-strain housing effects on aging in female mice - Chih-Lin Lee; Yu-Chiao Lin; Tsung-Han Kuo (Biogerontology, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

Comparative Analysis of Improved YOLO v5 Models for Corrosion Detection in Coastal Environments - Qifeng Yu; Yudong Han; Xinjia Gao; Wuguang Lin; Yi Han (Journal of Marine Science and Engineering, 2024)
Coastal areas face severe corrosion issues, posing significant risks and economic losses to equipment, personnel, and the environment. YOLO v5, known for its speed, accuracy, and ease of deployment, has been employed for the rapid detection and identification of marine corrosion. However, corrosion images often feature complex characteristics and high variability in detection targets, presenting significant challenges for YOLO v5 in recognizing and extracting corrosion features. To improve the detection performance of YOLO v5 for corrosion image features, this study investigates two enhanced models: EfficientViT-NWD-YOLO v5 and Gold-NWD-YOLO v5. These models specifically target improvements to the backbone and neck structures of YOLO v5, respectively. The performance of these models for corrosion detection is analyzed in comparison with both YOLO v5 and NWD-YOLO v5. The evaluation metrics including precision, recall, F1-score, Frames Per Second (FPS), pre-processing time, inference time, non-maximum suppression time (NMS), and confusion matrix were used to evaluate the detection performance. The results indicate that the Gold-NWD-YOLO v5 model shows significant improvements in precision, recall, F1-score, and accurate prediction probability. However, it also increases inference time and NMS time, and decreases FPS. This suggests that while the modified neck structure significantly enhances detection performance in corrosion images, it also increases computational overhead. On the other hand, the EfficientViT-NWD-YOLO v5 model shows slight improvements in precision, recall, F1-score, and accurate prediction probability. Notably, it significantly reduces inference and NMS time, and greatly improves FPS. This indicates that modifications to the backbone structure do not notably enhance corrosion detection performance but significantly improve detection speed. From the application perspective, YOLO v5 and NWD-YOLO v5 are suitable for routine corrosion detection applications. Gold-NWD-YOLO v5 is better suited for scenarios requiring high precision in corrosion detection, while EfficientViT-NWD-YOLO v5 is ideal for applications needing a balance between speed and accuracy. The findings can guide decision making for corrosion health monitoring for critical infrastructure in coastal areas.

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Determination of 3-nitropropionic acid in sugarcane using dispersive solid-phase extraction and gas chromatography–atmospheric pressure chemical ionization–tandem mass spectrometry - Zuolong Yu; Yu Lin; Xiujin Zhou; Yao Chen; Zhijin Yang; Chao Han; Yan Shen (Food Chemistry, 2024)

Corrigendum to “In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration” [Chem. Eng. J. 496 (2024) 154330] - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

High entropy catalysts in electrolytic water splitting: A review from properties to applications - Zhi-Jie Zhang; Ning Yu; Yi-Lin Dong; Guanqun Han; Han Hu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Allelopathy research on the continuous cropping problem of poplar (populus) - Tao Song; Jia-Xu Chen; Lin-Miao Shan; Yu-Chen Qian; Mo-Xian Chen; Jian-Gang Han; Fu-Yuan Zhu (Phytochemistry Reviews, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Emergency room visits (ERVs) among occupational groups associated with ambient conditions in Taiwan - Ayushi Sharma; Kang Yajing; Min-Chun Lin; Liwen Deng; Yu-Kai Lin; Lin-Han Chianghsieh; Fung-Chang Sung; Yu-Chun Wang (International Archives of Occupational and Environmental Health, 2024)

Research on Hydrodynamics of Trans-Media Vehicles Considering Underwater Time-Varying Attitudes - Shuo Liu; Chihao Du; Yijie Han; Yu Zhang; Wanglin Lin; Yong Cai; Tao Wang (Journal of Marine Science and Engineering, 2024)
A trans-media vehicle is a new type of equipment that can adapt to two environments, water and air, to maintain optimal hydrodynamic and aerodynamic performance. However, no matter what kind of trans-media vehicle, its dynamics are much more complicated when traversing the interface of the medium, as the parameters are time-varying due to the change in ambient medium and vehicle attitudes. In order to improve the stability and performance of the trans-media vehicle in complex environments, an accurate mathematical model is established to characterize the dynamics of the trans-media vehicle in this process in this study. The time-varying hydrodynamic coefficients with different attitudes or depths are obtained using computational fluid dynamics software. The mathematical model is solved iteratively using a Runge–Kutta solver to calculate the dynamic response. A prototype of trans-media vehicle is fabricated, and motion experiments are performed in the pool. The experimental results confirm the effectiveness of the established model and lay the foundation for further controller design, providing a reference for the dynamic modeling of other similar equipment operating in complex environments. The primary novelty of this study lies in the fact that the established dynamic model considers the complex interaction between the attitude of the trans-media vehicle and the inherent different properties of water and air and utilizes computational fluid dynamics software to accurately obtain time-varying coefficients under different attitudes and depths. This approach not only recognizes the criticality of orientation-dependent hydrodynamic coefficients but also incorporates their temporal variations, which were often overlooked in previous studies.

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Emamectin benzoate exposure induced carp kidney injury by triggering mitochondrial oxidative stress to accelerate ferroptosis and autophagy - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Pesticide Biochemistry and Physiology, 2024)

Developmental toxicity of the neonicotinoid pesticide clothianidin to the larvae of the crustacean Decapoda, Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Journal of Hazardous Materials, 2024)

Enhanced rheological and 3D-printing properties of high internal phase emulsions stabilized by egg white microgels synergized with konjac gum/xanthan gum - Xiliang Yu; Lin Han; Qinggang Xu; Shengjie Li; Sangeeta Prakash; Xiuping Dong (Food Hydrocolloids, 2024)

Awakening dumb Mn2+ mechanoluminescence site to achieve force, temperature and time-domain induced color tuning via trap-assisted energy transfer - Jiaqi Ou; Shuangqiang Fang; Haoliang Cheng; Dongjie Han; Qiangqiang Zhu; Yue Zhai; He Lin; Jiali Yu; Renjie Xu; RongJun Xie; Le Wang (Chemical Engineering Journal, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

A temperature compensated fiber probe for highly sensitive detection in virus gene biosensing - Xiaopeng Han; Yu Zhang; Yundong Zhang; Qinghao Song; Wuliji Hasi; Siyu Lin; Fan Wang (Analytica Chimica Acta, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

Global diversity of airborne pathogenic bacteria and fungi from wastewater treatment plants - Ying Wang; Wenwen Wang; Xuezheng Yu; Zixuan Wang; Ziyu Zhou; Yunping Han; Lin Li (Water Research, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

BaO-modified finger-like nickel-based anode for enhanced performance and durability of direct carbon solid oxide fuel cells - Lin Li; Yujiao Xie; Tingting Han; Jinjin Zhang; Fangyong Yu; Gen Li; Jaka Sunarso; Naitao Yang; Yongdan Li (Fuel, 2024)

Detection and Analysis of Corrosion on Coated Metal Surfaces Using Enhanced YOLO v5 Algorithm for Anti-Corrosion Performance Evaluation - Qifeng Yu; Yudong Han; Wuguang Lin; Xinjia Gao (Journal of Marine Science and Engineering, 2024)
This study addresses the severe corrosion issues in the coastal regions of southern China by proposing an improved YOLO v5-GOLD-NWD model. Utilizing corrosion data from the National Center for Materials Corrosion and Protection Science of China, a dataset was constructed for metal-surface corrosion under different protective coatings. This dataset was used for model training, testing, and comparison. Model accuracy was validated using precision, recall, F1 score, and prediction probability. The results demonstrate that the proposed improved model exhibits better identification precision in metal corrosion detection, achieving 78%, a 4% improvement compared to traditional YOLO v5 models. Additionally, through identification and statistical analysis of corrosion image datasets from five types of coated metal specimens, it was found that powder epoxy coating, fluorocarbon coating, epoxy coating, and chlorinated rubber coating showed good corrosion resistance after 24 months of exposure. Conversely, Wuxi anti-fouling coating exhibited poor corrosion resistance. After 60 months of natural exposure, the powder epoxy coating specimens had the highest corrosion occurrence probability, followed by chlorinated rubber coating and epoxy coating, with fluorocarbon coating showing relatively lower probability. The fluorocarbon coating demonstrated relatively good corrosion resistance at both 24 and 60 months of exposure. The findings of this study provide a theoretical basis for enhancing the corrosion protection effectiveness of steel structures in coastal areas.

Next-generation neonicotinoid: The impact of cycloxaprid on the crustacean decapod Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Chemosphere, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Different microbial functional traits drive bulk and rhizosphere soil phosphorus mobilization in an alpine meadow after nitrogen input - Bing Han; Yicheng He; Ji Chen; Yufei Wang; Lina Shi; Zhenrong Lin; Lu Yu; Xiaoting Wei; Wantong Zhang; Yiyi Geng; Xinqing Shao; Shangang Jia (Science of The Total Environment, 2024)

Deep learning-based forecasting model for chlorophyll-a response to tropical cyclones in the Western North Pacific - Haobin Cen; Guoqing Han; Xiayan Lin; Yu Liu; Han Zhang (Ocean Modelling, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Species selection as a key factor in the afforestation of coastal salt-affected lands: Insights from pot and field experiments - Tzu-Hao Su; Yang Shen; Yao-Yu Chiang; Yu-Ting Liu; Han-Ming You; Hung-Chih Lin; Kuan-Ning Kung; Yao-Moan Huang; Chih-Ming Lai (Journal of Environmental Management, 2024)

Enzymatic impregnation by high hydrostatic pressure for preparing shape-retaining softened broccoli and carrot - Yu-Hsiang Wu; Bo-Chi Huang; Yan-Han Lin; Chung-Yi Wang (Food Bioscience, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

MetaIBM: A Python-based library for individual-based modelling of eco-evolutionary dynamics in spatial-explicit metacommunities - Jian-Hao Lin; Yu-Juan Quan; Bo-Ping Han (Ecological Modelling, 2024)

Reconstruction of Fe sacrifice protective layer enables highly effective CoP catalyst for hydrogen evolution reaction at high current density - Yingying Xu; Yingxia Zhao; Ming Sun; Wei Xie; Ying Wu; Gao Cheng; Yuanhong Zhong; Shenbo Han; Lin Yu (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Inhibitory effect of malonic acid on Microcystis aeruginosa: Cell morphology, oxidative stress and gene expression - Chunyang Tao; Xiaojun Niu; Dongqing Zhang; Yuejin Liu; Lingling Zhou; Yunhao Han; Yujing Mo; Kaixin Wu; Yu Lin; Zhang Lin (Algal Research, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Self-assembled C-Ag hybrid nanoparticle on nanoporous GaN enabled ultra-high enhancement factor SERS sensor for sensitive thiram detection - Hongpeng Zhou; Jiaoyan Qiu; Yunhong Zhang; Yanbo Liang; Lin Han; Yu Zhang (Journal of Hazardous Materials, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Efficient EVs separation and detection by an alumina-nanochannel-array-membrane integrated microfluidic chip and an antibody barcode biochip - Jiaoyan Qiu; Qindong Guo; Yujin Chu; Chunhua Wang; Hao Xue; Yu Zhang; Hong Liu; Gang Li; Lin Han (Analytica Chimica Acta, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

The different dynamic influences of Typhoon Kalmaegi on two pre-existing anticyclonic ocean eddies - Yihao He; Xiayan Lin; Guoqing Han; Yu Liu; Han Zhang (Ocean Science, 2024)
Using multi-source observational data and GLORYS12V1 reanalysis data, we conduct a comparative analysis of different responses of two warm eddies, AE1 and AE2 in the northern South China Sea, to Typhoon Kalmaegi during September 2014. The findings of our research are as follows: (1) for horizontal distribution, the area and the sea surface temperature (SST) of AE1 and AE2 decrease by about 31 % (36 %) and 0.4 °C (0.6 °C). The amplitude, Rossby number (Ro = relative vorticity / Coriolis parameter) and eddy kinetic energy (EKE) of AE1 increase by 1.3 cm (5.7 %), 1.4×10-2 (20.6 %) and 107.2 cm2 s−2 (49.2 %) after the typhoon, respectively, while AE2 weakens and the amplitude, Rossby number and EKE decrease by 3.1 cm (14.6 %), 1.6×10-2 (26.2 %) and 38.5 cm2 s−2 (20.2 %), respectively. (2) In the vertical direction, AE1 demonstrates enhanced convergence, leading to an increase in temperature and a decrease in salinity above 150 m. The response below the mixed-layer depth (MLD) is particularly prominent (1.3 °C). In contrast, AE2 experiences cooling and a decrease in salinity above the MLD. Below the MLD, it exhibits a subsurface temperature drop and salinity increase due to the upwelling of cold water induced by the suction effect of the typhoon. (3) The disparity in the responses of the two warm eddies can be attributed to their different positions relative to Typhoon Kalmaegi. Under the influence of negative wind stress curl outside the maximum wind radius (Rmax) of the typhoon, triggering negative Ekman pumping velocity (EPV) and quasi-geostrophic adjustment of the eddy, the warm eddy AE1, with its center to the left of the typhoon's path, further enhances the converging sinking of the upper warm water, resulting in its intensification. On the other hand, the warm eddy AE2, situated closer to the center of the typhoon, weakens due to the cold suction caused by the strong positive wind stress curl within the typhoon's Rmax. The same polarity eddies may have different response to typhoons. The distance between eddies and typhoons, eddy intensity, and the background field need to be considered.

Variations in the Upper Ocean Heat Content of the Southern Canadian Basin - Yu Liu; Changcheng Ye; Haobin Cen; Xiayan Lin; Guoqing Han (Journal of Marine Science and Engineering, 2024)
The marine environment of the Arctic Ocean has changed rapidly in recent decades. We used reanalysis data and observational data to explore the variations in the upper ocean heat content (OHC) of the Canadian Basin (CB) and the variations in the temperature profiles of the Southern Canadian Basin (SCB). Both the reanalysis data and observational data show increasing trends for the OHC of the CB from 1993 to 2023. Compared to the World Ocean Atlas data (WOA 18/23), the reanalysis data (ORAS5 or GLORYS12V1) significantly underestimated the values of the upper OHC of the Canadian Basin. To explain the OHC differences, the Ice-Tethered Profiler (ITP) observational data were used to analyze the variations in the vertical temperature profiles. We found that the reanalysis data remarkably underestimated the maximum temperatures of the subsurface Pacific warm water and its increasing trend. Based on the short-term prediction results from the Bi-LSTM neural network, we forecasted that the upper OHC will continue to increase in the SCB, mainly due to the warming of the intermediate Atlantic warm water. The research results provide a valuable reference for assessing and improving climate-coupled models.

Development of magnetic fluorescence aptasensor for sensitive detection of saxitoxin based on Fe3O4@Au-Pt nanozymes - Lin Zhu; Wei Zeng; Yueqing Li; Yu Han; Jing Wei; Long Wu (Science of The Total Environment, 2024)

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Post-stroke Chinese pure alexia: linguistic features and neuropsychological profiles - Shen-yi Kuang; Yi Xu; Yu-yuan Wang; Zi-gao Wang; Qiang Dong; Xiang Han; Shi-Lin Yang (Acta Neurologica Belgica, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

A comprehensive evaluation of milk protein molecular weight distribution based on exclusion chromatography dataset - Yu Liu; Xiao-Yan Li; Ling Li; Yu-Qi Yin; Han-Lin Zhang; Kun-Long Wang; Jie Zhou; Yun Chen; Ying-Hua Zhang (Food Chemistry, 2024)

Experimental verification of seismic vibration control of high-rise buildings with friction-type multiple tuned mass dampers - Ging-Long Lin; Chi-Chang Lin; Tsung-Han Yang; Hao-Yu Lung (Engineering Structures, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Microbiota-mediated metabolic perturbations in the gut and brain of mice after microplastic exposure - Sheng-Han Lee; Wan-Yu Lin; Tsun-Jen Cheng (Chemosphere, 2024)

Triphenyl phosphate exposure impairs colorectal health by altering host immunity and colorectal microbiota - Changchun Ye; Zilu Chen; Wenhao Lin; Zepeng Dong; Jie Han; Jingyi Zhang; Xueqian Ma; Junhui Yu; Xuejun Sun; Ying Li; Jianbao Zheng (Chemosphere, 2024)

Acute septicemia and diagnostic evaluation of Aeromonas veronii infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Guilian Zeng; Yebing Yu; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2024)

Prediction of thermal conductivities of insulation materials under water immersion and freeze–thaw conditions for tunnels in cold regions - Fenglei Han; Zonghan Liu; Jiazheng Li; Wenbing Yu; Qixiang Yan; Yuanfu Zhou; Shuzhen Zhang; Lin Chen (Tunnelling and Underground Space Technology, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Preparation and 3D printing of high internal-phase Pickering emulsions stabilized by chicken egg white microgel - Xiliang Yu; Lin Han; Jiaqi Liu; Wenjia Jiang; Jinfeng Pan; Chenxu Yu; Xiuping Dong (Food Hydrocolloids, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Spatial patterns of light response parameters and their regulation on gross primary productivity in China - Yong Lin; Zhi Chen; Guirui Yu; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Wenxing Luo (Agricultural and Forest Meteorology, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Hydrological connectivity controls on the dynamics of particulate organic matter in a semi-enclosed mariculture bay - Aiqin Han; Jin-Yu Terence Yang; Mengli Chen; Zhenzhen Zheng; Xijie Yin; Hui Lin; Min Nina Xu; Shuh-Ji Kao (Aquaculture, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Effects of Aegilops longissima chromosome 1Sl on wheat bread-making quality in two types of translocation lines - Yuliang Qiu; Zhiyang Han; Ningtao Liu; Mei Yu; Shuangxi Zhang; Haiqiang Chen; Huali Tang; Zhiyong Zhao; Ke Wang; Zhishan Lin; Fangpu Han; Xingguo Ye (Theoretical and Applied Genetics, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Phenotypic characteristics and immune response of Procypris merus following challenge with aquatic isolate of Klebsiella pneumoniae - Wenyu Liao; Dongdong Wei; Mingzhu Liu; Lin Huang; Bingzheng Li; Yunyi Wei; Shuyu Han; Shuaishuai Huang; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2024)
Currently, aquaculture is a relatively mature industry; however, disease problems are continuously threatening the industry and hindering its development to a certain extent. Klebsiella pneumoniae is one of the zoonotic bacteria widely present in different hosts and has caused some degree of harm to the aquaculture industry, posing a potential threat to the water environment and indirectly also affecting human food safety issues. In this study, K. pneumoniae was isolated from the aquaculture environment, named as ELD, and subjected to pathogenic and immunological related studies. The results of the study showed that the strain carries at least four virulence‐related genes, magA , wabG , ureA and uge , and has developed resistance to at least seven antibacterial drugs, such as amoxicillin, doxycycline, rifampicin, and so on. Moreover, the strain is highly pathogenic and is capable of causing systemic clinical foci in Procypris merus . In addition, after infection with K. pneumoniae , the expression of IL‐1β, IL‐8, HSP70 and C2 was upregulated in P. merus as a whole, whereas the expression of TNF‐α did not change significantly in any of the tissues, which might be a kind of immune response of P. merus against K. pneumoniae infection. This study provides an important theoretical basis for the in‐depth exploration of the pathogenic mechanism of K. pneumoniae in fish and the immune response that occurs after the disease is contracted in fish, as well as theoretical support for the development of effective preventive and therapeutic strategies against K. pneumoniae ‐infected aquatic animals in the future.

Two-dimensional, high-resolution imaging of pH dynamics in the phyllosphere of submerged macrophyte using a new Nano-optode - Jianyu Lin; Yu Sun; Hao Zhang; Qiushi Shen; Li Xu; Qingfei Zeng; Yaling Su; Chao Han (Science of The Total Environment, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Evolutionary traits and functional roles of chemokines and their receptors in the male pregnancy of the Syngnathidae - Han Jiang; Zhanwei Zhao; Haiyan Yu; Qiang Lin; Yali Liu (Marine Life Science & Technology, 2023)

Decoding the marine biogeochemical cycling of mercury by stable mercury isotopes - Lin Yang; Ben Yu; Deming Han; Kun Zhang; Hongwei Liu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2023)

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Unraveling heterogeneity of dissolved organic matter in highly connected natural water bodies at molecular level - Guan-Lin Chen; Chen Qian; Bo Gong; Meng Du; Rui-Zhe Sun; Jie-Jie Chen; Han-Qing Yu (Water Research, 2023)

Unlocking the potential of resuscitation-promoting factor for enhancing anaerobic microbial dechlorination of polychlorinated biphenyls - Zhen Han; Aiqin Hou; Xiaolin Cai; Mengqi Xie; Faqian Sun; Chaofeng Shen; Hongjun Lin; Haiying Yu; Xiaomei Su (Science of The Total Environment, 2023)

Investigation of the effects of chemical modification and oxidative aging on the properties and compatibility of rubber asphalt based on thermodynamic principles - Jing Li; Hao Jiang; Fuhu Han; Zibo Lin; Zhenxia Zhao; Xin Jin; Yu Liu (Journal of Cleaner Production, 2023)

Study on potential antigenicity and functional properties of whey protein treated by high hydrostatic pressure based on structural analysis - Xin-Xin Yu; Xiao-Hui Wang; Sheng-Ao Zhang; Ying-Hua Zhang; Han-Lin Zhang; Yu-Qi Yin (Food Research International, 2023)

Carrageenan addition improves the melting temperature and 3D printing performance of the gelatin system - Yue Wang; Lin Han; Wanying Yu; Weiping Zhao; Jinfeng Pan; Sangeeta Prakash; Xiuping Dong (Food Hydrocolloids, 2023)

Oxidation of Sb(III) by Shewanella species with the assistance of extracellular organic matter - Kai-Li Wang; Di Min; Guan-Lin Chen; Dong-Feng Liu; Han-Qing Yu (Environmental Research, 2023)

Oxygen-producing composite dressing activated by photothermal and piezoelectric effects for accelerated healing of infected wounds - Yen-Han Lai; Snigdha Roy Barman; Anindita Ganguly; Arnab Pal; Jui-Han Yu; Syun-Hong Chou; E-Wen Huang; Zong-Hong Lin; San-Yuan Chen (Chemical Engineering Journal, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Design of rich defects carbon coated MnFe2O4/LaMnO3/LaFeO3 heterostructure nanocomposites for broadband electromagnetic wave absorption - Xinyang Liu; Lin He; Guanghui Han; Jie Sheng; Yongsheng Yu; Weiwei Yang (Chemical Engineering Journal, 2023)

Enhanced dual-mode electrochemical zinc ion sensing by electric field-driven bi-directional mass transport - Yuzhen Huang; Kai Zhang; Xiaoshuang Chen; Xiaohui Yan; Jiaoyan Qiu; Yu Zhang; Lin Han (Chemical Engineering Journal, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Association between Asbestos Exposure and the Incidence of Kidney Cancer: a Weight-of-Evidence Evaluation and Meta-analysis - Fu-Shiuan Whitney Lee; Yu-Han Chen; Ngoc Dang Tran; Cheng-Kuan Lin; Le An Pham (Current Environmental Health Reports, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

PxRdl2 dsRNA increased the insecticidal activities of GABAR-targeting compounds against Plutella xylostella - Ben-Jie Li; Kun-Kun Wang; Ye Yu; Jia-Qi Wei; Jian Zhu; Jia-Li Wang; Fei Lin; Han-Hong Xu (Pesticide Biochemistry and Physiology, 2023)

Investigation of the fall armyworm (Spodoptera frugiperda) gut microbiome and entomopathogenic fungus-induced pathobiome - Yao-Chia Liu; Tzu-Han Chen; Yu-Feng Huang; Chang-Lin Chen; Yu-Shin Nai (Journal of Invertebrate Pathology, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

Meningeal lymphatics restoration and neurovascular protection synergistically improve traumatic brain injury treatment - Jingquan Lin; Hangxiang Sun; Hongjie Jiang; Rui Xue; Bing Qin; Jianan Lu; Zhoule Zhu; Chengwei Cai; Jiawei Han; Jianmin Zhang; Xiaohua Yu; Junming Zhu (Chemical Engineering Journal, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Comparison of nutritional quality, flesh quality, muscle cellularity, and expression of muscle growth-related genes between wild and recirculating aquaculture system (RAS)-farmed black rockfish (Sebastes schlegelii) - Xin Gao; Haojie Zhai; Zuxiang Peng; Jinxi Yu; Lin Yan; Wei Wang; Tongjun Ren; Yuzhe Han (Aquaculture International, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Numerical analysis of a modified combined volumetric filtered concentrating PV/T system using MCRT and FVM coupled method - Lin Tu; Yu Ma; Xinyue Han; Mingze Zhu (Journal of Cleaner Production, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Assessment of various conditions for the simultaneous determination of US EPA and EU priority PAHs in coffee samples and their PAHs consumption risk - Yu-Fang Huang; Po-Lin Liao; Yi-Jun Lin; Shih-Han Huang; Yi-Hsieng Samuel Wu; Chia-Fang Teng; Deng-Jye Yang (Food Research International, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

Effect of curcumin on the formation of polycyclic aromatic hydrocarbons in grilled chicken wings - Huixin Tian; Jing Yu; Min Li; Jing Li; Yifeng Lu; Xiaobo Yu; Shaoyan Lin; Xianming Zeng; Xinglian Xu; Minyi Han (Food Chemistry, 2023)

An accurate and efficient method for simultaneous determination of 16 trichothecenes in maize and wheat by UHPLC-Q-Orbitrap-HRMS combined one-step pretreatment with a novel isotope multipoint calibration strategy - Yu Wu; Jin Ye; Songshan Wang; Xiaomin Han; Li Li; Lin Zhu; Sen Li; Hongmei Liu; Yang Wang; Yi Shao; Songxue Wang (Food Control, 2023)

Combined exposure to lead and high-fat diet induced neuronal deficits in rats: Anti-neuroinflammatory role of SIRT1 - Mengchen Liu; Rundong Liu; Mingzhi Yang; Yue Ba; Qihong Deng; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (Food and Chemical Toxicology, 2023)

A fractional-order two-surface plasticity model for over-consolidated clays and its application to deep gallery excavation - Wei Cheng; Ren-Peng Chen; Zhen-Yu Yin; Han-Lin Wang; Fan-Yan Meng (Computers and Geotechnics, 2023)

Sulfonated polyhedral oligomeric silsesquioxane-cyclodextrin hybrid polymers for efficient removal of micropollutants from water - Hengye Li; Xingwei Han; Lin Zhang; Wenjie Yu; Wenwen Bie; Meijie Wei; Zhongxia Wang; Fenying Kong; Wei Wang (Carbohydrate Polymers, 2023)

Evaluation of key factors influencing urban ozone pollution in the Pearl River Delta and its atmospheric implications - Xiao-Yu Lin; Shi-Yong Xia; Yao Luo; Heng-Xiao Han; Ling-Yan He (Atmospheric Environment, 2023)

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

Synthesis of porous dimethoxypillar[5]arene knitted β-cyclodextrin copolymers for efficient adsorption of organic micropollutants - Hengye Li; Xingwei Han; Wenjie Yu; Lin Zhang; Wenwen Bie; Meijie Wei; Zhongxia Wang; Fenying Kong; Wei Wang (Carbohydrate Polymers, 2023)

RNA-Sequencing Reveals Gene Expression and Pathway Signatures in Umbilical Cord Blood Affected by Birth Delivery Mode - Yongjie Liu; Kun Sun; Yuexin Gan; Han Liu; Juehua Yu; Wei Xu; Lin Zhang; Dan Chen (Phenomics, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Coating zero valent iron onto hollow carbon spheres as efficient electrocatalyst for N2 fixation and neutral Zn-N2 battery - Huici Qiao; Yu Han; Lin Yao; Xin Xu; Jun Ma; Bin Wen; Jie Hu; Hao Huang (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Donor-acceptor engineered g-C3N4 enabling peroxymonosulfate photocatalytic conversion to 1O2 with nearly 100% selectivity - Zonglin Weng; Yuanfang Lin; Bin Han; Xinfei Zhang; Qin Guo; Yu Luo; Xinwen Ou; Yang Zhou; Jin Jiang (Journal of Hazardous Materials, 2023)

Rational design of donor-acceptor engineered g-C3N4 for boosted H2O2 production via photocatalytic O2 reduction - Yu Luo; Yuanfang Lin; Zonglin Weng; Bin Han; Yang Zhou; Xinwen Ou; Jin Jiang (Journal of Environmental Chemical Engineering, 2023)

Effect of ferulic acid covalent conjugation on the functional properties and antigenicity of β-lactoglobulin - Yu-Ting Xue; Ya-Ning Han; Yan Wang; Ying-Hua Zhang; Yu-Qi Yin; Bo-Hao Liu; Han-Lin Zhang; Xin-Huai Zhao (Food Chemistry, 2023)

Two-phase transition induced cation-disordered Li-reactive bi-metallic phosphides enabling high-performance Li-storage - Yanhong Li; Lei Zhang; Jianbin Deng; Hung-Yu Yen; Songliu Yuan; Jeng-Han Wang; Chunfu Lin; Meilin Liu; Wenwu Li (Chemical Engineering Journal, 2023)

Direct conversion of water to hydrogen peroxide on single electrode towards partial oxidation of propylene - Runfei Xu; Haoyang Huang; Wenjing Wang; Lei Ding; Qiang Lin; Jinbing Li; Yu Zhang; Yongsheng Han; Jianguo Wang; Xiaohua Lu (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Effects of copper oxide nanoparticles on soil diazotrophic communities in maize rhizosphere - Jiling Cao; Zhiyuan Liu; Haiying Zhao; Faying Lai; Yu Han; Xiangui Lin (Journal of Soils and Sediments, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

The changes of chemical molecular components in soil organic matter are associated with fungus Mortierella capitata K. - Fang Li; Lin Chen; Zhan-Hui Zhao; Yue Li; Hai-You Yu; Yi Wang; Jia-Bao Zhang; Yan-Lai Han (Soil and Tillage Research, 2023)

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

Low-crystalline Ni(OH)2 ultrathin nanosheets upcycled from solid wastes for efficient photoconversion of low-concentration CO2 - Bin Han; Yuanfang Lin; Yu Luo; Weizhen Liu; Xueming Liu; Zonglin Weng; Xinwen Ou; Zhang Lin (Chemical Engineering Journal, 2023)

Corrigendum to “Discovery and characterization of the flavonoids in Cortex Mori Radicis as naturally occurring inhibitors against intestinal nitroreductases” [Chem. Biol. Interact. 368 (2022) 110222] - Xi Chen; Yue Han; Lu Chen; Qian-Lin Tian; Yu-Ling Yin; Qi Zhou; Shi-Zhu Zang; Jie Hou (Chemico-Biological Interactions, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

Perfluorooctanoic acid and perfluorooctanesulfonic acid induce immunotoxicity through the NF-κB pathway in black-spotted frog (Rana nigromaculata) - Zhiquan Liu; Huikang Lin; Yueyue Zheng; Yixuan Feng; Chaoli Shi; Ruoxin Zhu; Xingyao Shen; Yu Han; Hangjun Zhang; Yuchi Zhong (Chemosphere, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Enrofloxacin exposure induces anxiety-like behavioral responses in zebrafish by affecting the microbiota-gut-brain axis - Dandan Tian; Wei Shi; Yihan Yu; Weishang Zhou; Yu Tang; Weixia Zhang; Lin Huang; Yu Han; Guangxu Liu (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

A self-assembly hydrophobic oCDs/Ag nanoparticles SERS sensor for ultrasensitive melamine detection in milk - Jiaoyan Qiu; Yujin Chu; Qihang He; Yingkuan Han; Yu Zhang; Lin Han (Food Chemistry, 2023)

Comprehensive application possibility: Construction hydrophilic, amphiphilic and hydrophobic system of modified zein by enzymatic or cysteine modification - An-Qi Zhang; Xiao-Yan Li; Bo-Hao Liu; Yu-Qi Yin; Han-Lin Zhang; Ying-Hua Zhang (Food Hydrocolloids, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

Cross-Slope Transport by a Mesoscale Anticyclone in the Northern South China Sea - Xiayan Lin; Guixi Wang; Guoqing Han; Yu Liu; Han Zhang; Xiaomei Liao; Qiyan Ji (Journal of Marine Science and Engineering, 2023)
Cross-slope eddies play an important role in the exchange of water, salt, heat, nutrients, chlorophyll, phytoplankton and other biogeochemical elements between basin and shelf in the South China Sea. The cross-slope transport process by a mesoscale anticyclonic eddy is studied by ROMS model and satellite data. The 1000 m isobath was considered as a proxy for the slope. The anticyclone shows different features at different places on the slope: (a) the volume transport at the northeast of the slope was off-slope, while at the southwest was on-slope; (b) both on and off-slope transports were greatly enhanced during the cross-slope process, and gradually weakened after crossing the slope. The total cross-slope water transport was 5.97 Sv, which was higher than the along-slope component with −0.58 Sv. The Eulerian results also showed that enhanced cross-slope transport was related to the distance between the eddy and slope, the eddy radius, and the eccentricity of the eddy. The offline passive tracer experiment showed that particles were floating up during and after the crossing process, mainly due to the strong Ekman pumping.

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Landslide-impacted soils recover faster biologically than chemically or physically, though recovery also varies with forest type in subtropical China - Jian Li; Lan Xiao; Jonathan D. Bakker; Qinghu Luo; Hang Yu; Jianzhao Wu; Songyang Li; Loretta Pedersen; Can Chen; Tao Hong; Han Lin; Daojie Wang; et al. (Soil and Tillage Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Comparative pulmonary toxicity assessment of tungsten trioxide and tungsten trioxide hydrate nanoparticles - Hsin Her Yu; Yi-Chun Chen; Han-Pang Su; Liliang Chen; Hung-Hsiang Chen; Kun-Yi Andrew Lin; Chia-Hua Lin (Science of The Total Environment, 2023)

Electron beam irradiation pretreatment enhances the formation of granular starch-phenolics complexes - Yuefeng Huang; Qiuyan Liu; Jiangtao Yu; Qiang Zhang; Caian He; Lin Han; Min Wang (Food Research International, 2023)

Identification of ISG15 in golden pompano, Trachinotus ovatus, and its role in virus and bacteria infections - Lin Huang; Yuan Cheng; Shuyu Han; Mingzhu Liu; Qing Yu; Hongling Wei; Jinzhao He; Pengfei Li (Fish & Shellfish Immunology, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

K+ and CeO2 nanoparticles modified OMS-2 nanorods for enhanced activity and stability of photocatalytic toluene oxidation: K+ charge modulation and mechanistic investigation - Pingping Yu; Nan Li; Weixin Zou; Xiaoqian Wei; Jiawei Ji; Li Han; Yandi Cai; Wei Tan; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Significant Wave Height Prediction in the South China Sea Based on the ConvLSTM Algorithm - Lei Han; Qiyan Ji; Xiaoyan Jia; Yu Liu; Guoqing Han; Xiayan Lin (Journal of Marine Science and Engineering, 2022)
Deep learning methods have excellent prospects for application in wave forecasting research. This study employed the convolutional LSTM (ConvLSTM) algorithm to predict the South China Sea (SCS) significant wave height (SWH). Three prediction models were established to investigate the influences of setting different parameters and using multiple training data on the forecasting effects. Compared with the SWH data from the China–France Ocean Satellite (CFOSAT), the SWH of WAVEWATCH III (WWIII) from the pacific islands ocean observing system are accurate enough to be used as training data for the ConvLSTM-based SWH prediction model. Model A was preliminarily established by only using the SWH from WWIII as the training data, and 20 sensitivity experiments were carried out to investigate the influences of different parameter settings on the forecasting effect of Model A. The experimental results showed that Model A has the best forecasting effect when using three years of training data and three hourly input data. With the same parameter settings as the best prediction performance Model A, Model B and C were also established by using more different training data. Model B used the wind shear velocity and SWH as training and input data. When making a 24-h SWH forecast, compared with Model A, the root mean square error (RMSE) of Model B is decreased by 17.6%, the correlation coefficient (CC) is increased by 2.90%, and the mean absolute percentage error (MAPE) is reduced by 12.2%. Model C used the SWH, wind shear velocity, wind and wave direction as training and input data. When making a 24-h SWH forecast, compared with Model A, the RMSE of Model C decreased by 19.0%, the CC increased by 2.65%, and the MAPE decreased by 14.8%. As the performance of the ConvLSTM-based prediction model mainly rely on the SWH training data. All the ConvLSTM-based prediction models show a greater RMSE in the nearshore area than that in the deep area of SCS and also show a greater RMSE during the period of typhoon transit than that without typhoon. Considering the wind shear velocity, wind, and wave direction also used as training data will improve the performance of SWH prediction.

Nutrient distributions and nitrogen-anomaly (N*) in the tropical North Pacific Ocean - Aiqin Han; Yu Wang; Yunlong Huo; Cai Lin; Kaiwen Zhou; Fangfang Kuang; Hui Lin (Acta Oceanologica Sinica, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Three-dimensional characteristics of mesoscale eddies simulated by a regional model in the northwestern Pacific Ocean during 2000–2008 - Guijing Yang; Xiayan Lin; Guoqing Han; Yu Liu; Gengxin Chen; Jianhui Wang (Acta Oceanologica Sinica, 2022)

Spatio-temporal analysis of east greenland polar front - Yu Liu; Jianhui Wang; Guoqing Han; Xiayan Lin; Guijing Yang; Qiyan Ji (Frontiers in Marine Science, 2022)
The East Greenland Polar Front (EGPF) is an important front with strong salinity and temperature gradients in the Nordic Seas. It is formed by the interaction between Arctic-origin and Atlantic-origin water. The variations of EGPF are closely linked with sea ice melting and heat content transport associated with North Atlantic water recirculation. For a three-dimensional (3D) daily analysis, we use the global ocean eddy resolution reanalysis product (GLORYS12V1) from 1993 to 2018 to calculate the salinity and temperature horizontal gradient in the upper ocean and obtain the spatiotemporal distribution and intensity characteristics of EGPF. After assessment, the thresholds of the salinity and temperature fronts are set to 0.04 psu/km and 0.09°C/km, respectively. Compared with satellite observations of sea ice concentration, a significant spatial relationship is observed between the main position of EGPF and the ice edge before the sea ice shrinks to the continental shelf sea area. Affected by the freshening of the Arctic-origin water due to the melting of the sea ice, the intensity and area of EGPF show significant seasonal variations. Against the background of global warming, the sea ice area presents an obvious decreasing trend in the Greenland Sea. The melting of sea ice increased annually every summer from 1998 to 2018. The heat content transport of the Atlantic-origin water has also increased in recent years. The 3D characteristics (intensity and volume) of EGPF as salinity and temperature fronts exhibit increasing trends.

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Propagation and Separation of Downslope Gravity Currents over Rigid and Emergent Vegetation Patches in Linearly Stratified Environments - Ying-Tien Lin; Yi-Qi Ye; Dong-Rui Han; Yu-Jia Chiu (Journal of Marine Science and Engineering, 2022)
Large eddy simulation (combined with the mixture model) and laboratory experiment were used to investigate the impact of emergent and rigid vegetation on the dynamics of downslope gravity currents in stratified environments. The reliability of the numerical model was assessed with the corresponding laboratory measurements. The results show that the vegetation cylinders lead to severe lateral non-uniformity of the current front, causing more evident lobe and cleft structures. In stratified environments, the smaller driving force leads to less propagating velocity until the current separates from the slope. The transition point (from acceleration to deceleration phases) of current velocity appears earlier as the vegetation becomes denser. The peak value of the bulk entrainment coefficient Ebuik is inversely proportional to the vegetation density, while the final converged value of Ebuik is proportional to the vegetation density. Vegetation patches make the degree of fluctuation of the instantaneous entrainment coefficient Einst more intense, and even negative values appear locally, indicating that the gravity current is detrained into the ambient fluid. The velocity profiles of gravity current develop multi-peak patterns in stratified environments due to fingering intrusive patterns. Our analysis reveals that as the vegetation density increases, the generated wakes behind vegetation cylinders increase local entrainment and mixing, causing the density of current flow from vegetation to decrease and reach the neutral buoyancy layer of ambient fluids earlier, finally leading to a smaller separation depth.

The lining responses for shallow mountain tunnels subjected to frost heaving - Xian-zhang Ling; Yuan Yu; Liang Tang; Lin Geng; Xiao Han (Journal of Mountain Science, 2022)

Research on hoop capacity of composite foundation of discarded rubber tires - Feng-Chi Wang; Jun Li; Zhen-Huan Lin; Pei-Pei Tian; Han-Yu Zhao (European Journal of Environmental and Civil Engineering, 2022)

Current Dependent Dispersal Characteristics of Japanese Glass Eel around Taiwan - Kuan-Mei Hsiung; Yen-Ting Lin; Yu-San Han (Journal of Marine Science and Engineering, 2022)
Japanese eel larvae are passively transported to the East Asian Continental Shelf by the North Equatorial Current, Kuroshio and Kuroshio intrusion currents, and coastal currents. Previous studies have investigated the dispersal characteristics and pathways of Japanese glass eels. However, there are still limitations in these studies. According to long-term (2010–2020) catch data from the Fisheries Agency in Taiwan, the distribution and time series of glass eels recruitment to Taiwan are closely related to the surrounding ocean currents. Recruitment begins in eastern Taiwan via the mainstream Kuroshio and in southern Taiwan via the Taiwan Strait Warm Current. In central Taiwan, recruitment occurs from southern Taiwan, as well as from mainland China via the southern branch of the China Coast Current (CCC). The latest recruitment occurred in northern Taiwan and mainly comprised glass eels from mainland China via the northern branch of the CCC. A stronger monsoon during the La Niña phase could affect the recruitment time series in northern and eastern Taiwan. This study suggests that the recruitment directionality of glass eels is an indicator of the flow field of ocean/coastal currents and elucidates the dispersal characteristics of glass eels in the waters around Taiwan.

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Kinetics and Size Effects on Adsorption of Cu(II), Cr(III), and Pb(II) Onto Polyethylene, Polypropylene, and Polyethylene Terephthalate Microplastic Particles - Xiaoxin Han; Shiyu Wang; Xue Yu; Rolf D. Vogt; Jianfeng Feng; Lifang Zhai; Weiqi Ma; Lin Zhu; Xueqiang Lu (Frontiers in Marine Science, 2021)
Due to its small size, large specific surface area and hydrophobicity, microplastics, and the adsorbed contaminants may together cause potential negative effects on ecosystems and human beings. In this study, kinetics and size effects on adsorption of Cu(II), Cr(III), and Pb(II) onto PE, PP and PET microplastic particles were explored. Results indicated that the PE and PET microplastics have the higher adsorption capacity for Cu(II), Cr(III), and Pb(II) than that for PP microplastic. The adsorption capacity was affected by microplastic types and metal species. Among the three metals, Pb(II) had the largest adsorption amount on microplastic particles, especially on PET particles. Moreover, the adsorption capacities of microplastics increase with the decrease of particle size. The metal adsorption capacity of <0.9 mm microplastics is greater than that of 0.9–2 mm and 2–5 mm microplastics. The size effect on metal adsorption was largest for PE microplastic. More attention should be paid in case of the coexistence of heavy metals and tiny PE and PET microplastics in the environment.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Dynamic Regulation of Ions and Amino Acids in Adult Asian Hard Clams Meretrix lusoria Upon Hyperosmotic Salinity - Chia-Hao Lin; Po-Ling Yeh; Yu-Chun Wang; Tsung-Han Lee (Frontiers in Marine Science, 2021)
The dynamic regulation of ions and amino acids in the gills and mantle of the Asian hard clam, Meretrix lusoria , following the exposure to a hyperosmotic environment was hitherto unclear. The present study revealed that the osmolality as well as the Na + and Cl – concentrations in the hemolymph were significantly increased 3 h after transferring the clams from an environment with the salinity of their natural habitat (brackish water; BW; 20‰) to one with hyperosmotic salinity (seawater; 35‰). In addition, we found that the specific activities of Na + /K + -ATPase, a key enzyme that plays a significant role in cell osmoregulation, in the gills and mantle of clams were significantly increased at 72 and 12 h post-transfer, respectively, during acclimation to hyperosmotic salinity. Similarly, the contents of free amino acids (FAAs) such as taurine, alanine, and glycine were significantly elevated during hyperosmotic salinity acclimation. Previous research indicates that taurine is the most abundant FAA in the gills and mantles of Asian hard clams and that the taurine transporter (TAUT) plays an important role in taurine accumulation. The present study showed that TAUT mRNA and protein expression were significantly and transiently increased in the mantle of Asian hard clams following exposure to seawater; although the expression of TAUT mRNA in the gills of Asian hard clams was also transiently stimulated by exposure to hyperosmotic salinity, the relative TAUT protein abundance decreased only at later stages. Accordingly, the findings of this study improve our understanding of the dynamic processes of ion and amino acid regulation in the peripheral tissues of bivalves under hyperosmotic stress.

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Stenotrophomonas strain CPCC 101271, an intestinal lifespan-prolonging bacterium for Caenorhabditis elegans that assists in host resistance to “Bacillus nematocida” colonization - Rui Han; Yu Wang; Yang Deng; Yuqin Zhang; Lin Zhang; Qiuhong Niu (Archives of Microbiology, 2021)
The soil-dwelling, opportunistic pathogenic bacterium "Bacillus nematocida" B16 exhibits strong killing activities against a variety of pathogenic nematodes via a “Trojan horse” mechanism that can kill worm species like Caenorhabditis elegans . The bacterial strain CPCC 101271 was previously isolated from the intestines of C. elegans that were recovered from natural habitats and can serve as a probiotic for C. elegans , while also assisting in resistance to infection by the pathogenic strain B16. In this study, the lifespan of C. elegans fed with strain CPCC 101271 cells was extended by approximately 40% compared with that of worms fed with Escherichia coli OP50 cells. In addition, the colonization of C. elegans by the pathogenic bacterium "B. nematocida" B16 was inhibited when pre-fed with strain CPCC 101271. Metagenomic sequence analysis of intestinal microbiota of C. elegans fed with strain CPCC 101271 and infected with B16 revealed that pre-feeding worms with CPCC 101271 improved the diversity of the intestinal bacteria. Moreover, community structure significantly varied in coordination with Stenotrophomonas spp. and Bacillus spp. abundances when competition between strains CPCC 101271 and B16 was evaluated. In conclusion, the nematode microbiota strain CPCC 101271 assisted in its host resistance to colonization by the pathogen "Bacillus nematocida" and can also promote life span-prolongation in C. elegans. These results underscore that understanding the interactions between C. elegans microbiota and pathogens can provide new insights into achieving effective biological control of agricultural pests.

Size Effect and Anisotropy in a Transversely Isotropic Rock Under Compressive Conditions - Kaihui Li; Zhen-Yu Yin; Dongya Han; Xiang Fan; Rihong Cao; Hang Lin (Rock Mechanics and Rock Engineering, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Integration of small RNAs, degradome, and transcriptome sequencing provides insights into the differences between Shizhu ginseng and Yuan ginseng - Mengyuan Peng; Yanlin Chen; Wenjuan Wang; Zhihua He; Wangqiang Dai; Zhiyun Lin; Zemin Yang; Mengjuan Gong; Yongqin Yin; Bin Han; Yu Zeng; Yingfang Wang (Journal of Plant Biochemistry and Biotechnology, 2021)
Panax ginseng is one of the most popular herbs which have been used as an important traditional Chinese medicine since ancient times. Yuan ginseng and Shizhu ginseng,which belong to P. ginseng , are widely used as substitutes for wild ginseng in clinical practice. Clinical practice has proved that the clinical efficacy of Shizhu ginseng is better than Yuan ginseng. However, current research cannot completely explain this phenomenon. Considering that small RNA may be one of the pharmacodynamic substances of P. ginseng , it is challenging to investigate differential miRNAs between Shizhu ginseng and Yuan ginseng. In this study, the transcriptome, small RNAome and degradome of P. ginseng were studied by high-throughput sequencing. A total of 63,875 unigenes and 43,950,137 small RNA clean reads were obtained from the roots of P. ginseng . Among 3206 differentially expressed genes, 1190 genes were up-regulated in Yuan ginseng when compared with Shizhu ginseng. 24 known differential miRNAs and 7 novel differential miRNAs were obtained. The 304 targets of 24 differentially expressed miRNA (17 known and 7 novel) families are mainly related to energy metabolism, biotic stress and disease immunity in ginseng itself. Through the association analysis of mRNA and miRNA, our work gives a better understanding of the difference between Yuan ginseng and Shizhu ginseng. Considering the cross-kingdom regulation of plant miRNAs, our results may provide a foundation for understanding the miRNA-dependent clinical efficacy in P. ginseng .

Human Methylmercury Exposure and Potential Impacts in Central Tibet: Food and Traditional Tibetan Medicine - Menghan Cheng; Maodian Liu; Dou Li; Qing Luo; Zhihao Zhang; Liuliang Yuan; Chenghao Yu; Han Xie; Huiming Lin; Qianru Zhang; De Ji; Xuejun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

At3g53630 encodes a GUN1-interacting protein under norflurazon treatment - Xing-Qi Huang; Lin-Juan Wang; Meng-Juan Kong; Na Huang; Xin-Ya Liu; Han-Yu Liang; Jia-Xin Zhang; Shan Lu (Protoplasma, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

The adaptability of typical precipitation ensemble prediction systems in the Huaihe River basin, China - Han Wang; Ping-an Zhong; Fei-lin Zhu; Qing-wen Lu; Yu-fei Ma; Sun-yu Xu (Stochastic Environmental Research and Risk Assessment, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Characterization of a Protease Hyper-Productive Mutant of Bacillus pumilus by Comparative Genomic and Transcriptomic Analysis - Yong-Cheng Liu; Lin-Li Han; Tian-Yu Chen; Yan-Bing Lu; Hong Feng (Current Microbiology, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

A Facile and Sensitive DNA Sensing of Harmful Algal Blooms Based on Graphene Oxide Nanosheets - Le Qiang; Yu Zhang; Chao Wu; Yingkuan Han; Suchun Wang; Yanyan Wang; Congcong Zhang; Guangzhou Liu; Qi Wu; Hong Liu; Ian R. Jenkinson; Jun Sun; et al. (Marine Biotechnology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Acute physiological responses to combined blood flow restriction and low-level laser - Yi-Ching Chen; Yu-Han Su; Yen-Ting Lin; Chien-Chun Huang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Effect of slope gradient on the subsurface water flow velocity of sand layer profile - Zhen Han; Xiao-yan Chen; Yu-han Huang; Bang-lin Luo; Hang Xing; Yong-chao Huang (Journal of Mountain Science, 2020)

Anti- β -amyloid aggregation activity of enantiomeric furolactone-type lignans from Archidendron clypearia (Jack) I.C.N. - Yu-Xi Wang; Bin Lin; Le Zhou; Zhi-Yang Yan; Han Zhang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Netrin-1 promotes the collective cell migration of liver cancer cells in a 3D cell culture model - Ping Han; Jingmei Liu; Yu Lei; Zhuoying Lin; Dean Tian; Wei Yan (Journal of Physiology and Biochemistry, 2019)

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

An experimental study of the impacts of solar radiation and temperature on mercury emission from different natural soils across China - Han Xie; Maodian Liu; Yipeng He; Huiming Lin; Chenghao Yu; Chunyan Deng; Xuejun Wang (Environmental Monitoring and Assessment, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Cloning, in silico characterization, subcellular localization, and expression of a heat shock cognate 70 kDa protein/gene (EjHsc70-2) from Eriobotrya japonica - Shoukai Lin; Ti Wu; Ming Li; Xiaoming Huang; Yanqing Zhang; Linxiao Han; Bisha Wu; Yu Chen; Suying Lin; Dahe Lin; Minlan Wu; Jincheng Wu (Acta Physiologiae Plantarum, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Evaluation of the diagnostic ratios of adamantanes for identifying seriously weathered spilled oils from simulated experiment and actual oil spills - Bin Han; Li Zheng; Qian Li; Faxiang Lin; Yu Ding (Environmental Geochemistry and Health, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Expansion and evolutionary patterns of GDSL-type esterases/lipases in Rosaceae genomes - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Jiangliu Yu; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Monitoring rubber plantation distribution on Hainan Island using Landsat OLI imagery - Pengpeng Han; Jinsong Chen; Yu Han; Lin Yi; Yannan Zhang; Xiaoli Jiang (International Journal of Remote Sensing, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Spa therapy (balneotherapy) relieves mental stress, sleep disorder, and general health problems in sub-healthy people - Bei Yang; Qi-zhong Qin; Ling-li Han; Jing Lin; Yu Chen (International Journal of Biometeorology, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

miR-137 and miR-491 Negatively Regulate Dopamine Transporter Expression and Function in Neural Cells - Xiaojian Jia; Feng Wang; Ying Han; Xuewen Geng; Minghua Li; Yu Shi; Lin Lu; Yun Chen (Neuroscience Bulletin, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Assessment of the seasonal variation of simulated Wyrtki jet over the tropical Indian Ocean in CMIP5 models - Lin Liu; Baochao Liu; Guoqing Han; Lin Feng; Xinfang Li; Weidong Yu (Arabian Journal of Geosciences, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

BM-MSCs and Bio-Oss complexes enhanced new bone formation during maxillary sinus floor augmentation by promoting differentiation of BM-MSCs - Qian Zhou; Bo-Han Yu; Wei-Cai Liu; Zuo-Lin Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

The Association Between Serum Selenium Levels with Rheumatoid Arthritis - Na Yu; Fang Han; Xiaojun Lin; Chun Tang; Jinghua Ye; Xiaoyan Cai (Biological Trace Element Research, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Controversial opinion: evaluation of EGR1 and LAMA2 loci for high myopia in Chinese populations - Fang-yu Lin; Zhu Huang; Ning Lu; Wei Chen; Hui Fang; Wei Han (Journal of Zhejiang University-SCIENCE B, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Research on Chinese public finance in response to domestic natural disasters - Yong-ling Zhang; Yan-nan Ma; An Chen; Yu-han Lin (Natural Hazards, 2015)

Production of Arachidonic and Eicosapentaenoic Acids by the Marine Oomycete Halophytophthora - Ka-Lai Pang; Han-Jia Lin; Hung-Yun Lin; Yu-Fen Huang; Yi-Min Chen (Marine Biotechnology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Removal of antineoplastic drugs cyclophosphamide, ifosfamide, and 5-fluorouracil and a vasodilator drug pentoxifylline from wastewaters by ozonation - Angela Yu-Chen Lin; Julia Han-Fang Hsueh; P. K. Andy Hong (Environmental Science and Pollution Research, 2015)

Seroprevalence and molecular detection of Mycoplasma ovipneumoniae in goats in tropical China - Guang Rong; Jun-Ming Zhao; Guan-Yu Hou; Han-Lin Zhou (Tropical Animal Health and Production, 2014)

Plant ferredoxin-like protein enhances resistance to bacterial soft rot disease through PAMP-triggered immunity in Arabidopsis thaliana - Yu-Han Su; Chuan-Yu Hong; Yi-Hsien Lin (European Journal of Plant Pathology, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

The histone deacetylase inhibitor vorinostat prevents TNFα-induced necroptosis by regulating multiple signaling pathways - Di Wang; Ming Zhao; Guozhu Chen; Xiang Cheng; Xiaoxi Han; Song Lin; Xuhui Zhang; Xiaodan Yu (Apoptosis, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

Organic acids on the growth, anatomical structure, biochemical parameters and heavy metal accumulation of Iris lactea var. chinensis seedling growing in Pb mine tailings - Yu-Lin Han; Su-Zhen Huang; Hai-Yan Yuan; Jiu-Zhou Zhao; Ji-Guang Gu (Ecotoxicology, 2013)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Retrieval of aerosol optical depth over bright targets in the urban areas of North China during winter - ShenShen Li; LiangFu Chen; JinHua Tao; Dong Han; ZhongTing Wang; Lin Su; Meng Fan; Chao Yu (Science China Earth Sciences, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Isolation and characterization of a long-chain acyl-coenzyme A synthetase encoding gene from the marine microalga Nannochloropsis oculata - Lin Zhang; Xiaolei Ma; Guanpin Yang; Baohua Zhu; Jichang Han; Wengong Yu; Kehou Pan (Journal of Applied Phycology, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Larval Japanese eel ( Anguilla japonica ) as sub‐surface current bio‐tracers on the East Asia continental shelf - YU‐SAN HAN; HENG ZHANG; YU‐HENG TSENG; MAO‐LIN SHEN (Fisheries Oceanography, 2012)
Larval Japanese eel (leptocephali) are passively transported from their spawning sites of the North Equatorial Current to the Kuroshio and its branch waters for 4–6 months before reaching the East Asian coasts. The larvae mainly stay within water depths between 50–150 m. The dispersal dynamics of larvae thus should reflect the sub‐surface oceanic currents on the East Asia continental shelf. An analysis of Japanese glass eel catch data in East Asian countries during 1985 to 2009, and for Taiwan from 1968 to 2008, indicates that the overall annual catch is generally correlated across countries of East Asia, and between north and west areas of Taiwan. The Kuroshio and its branch waters disperse glass eels throughout East Asian habitats, and the glass eel distribution matches the flow directionality of oceanic currents. Recruitment in western Taiwan occurs with a sequential southwestern to northwestern direction, suggesting that the Taiwan Strait Current penetrates the western coast of Taiwan in the sub‐surface layer in winter. The monthly averaged sub‐surface 50 m circulation pattern in the vicinity of Taiwan and modeled tracer experiments also support the northward winter sub‐surface current in Taiwan Strait. These results suggest that the larval Japanese eel could serve as a valuable bio‐tracer of sub‐surface currents, and the earlier recruitment dynamics of Japanese glass eels in Taiwan could be a good predictor for the subsequent catch in other East Asia areas.

Physiological response of Cu and Cu mine tailing remediation of Paulownia fortunei (Seem) Hemsl - Zao-Fa Jiang; Su-Zhen Huang; Yu-Lin Han; Jiu-Zhou Zhao; Jia-Jia Fu (Ecotoxicology, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

AURKB and MAPK involvement in the regulation of the early stages of mouse zygote development - Lin Xu; Tong Liu; Feng Han; ZhiHong Zong; GuoLi Wang; BingZhi Yu; Jie Zhang (Science China Life Sciences, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

A convolution algorithm to calculate differential cross sections of the Ring effect in the Earth’s atmosphere based on rotational Raman scattering - Dong Han; LiangFu Chen; Lin Su; JinHua Tao; ShenShen Li; Chao Yu; Ying Zhang; BaoHua He (Science China Earth Sciences, 2011)

Dexamethasone attenuates development of monocrotaline-induced pulmonary arterial hypertension - Wei Wang; Yu-lin Wang; Xiao-ying Chen; Yu-tang Li; Wei Hao; You-peng Jin; Bo Han (Molecular Biology Reports, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Investigation of the association between all-trans-retinol dehydrogenase (RDH8) polymorphisms and high myopia in Chinese - Yan-shu Yu; Lin-ling Wang; Ye Shen; Maurice K. H. Yap; Shea-ping Yip; Wei Han (Journal of Zhejiang University-SCIENCE B, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Angiotensin-converting enzyme 2 (ACE2) proteins of different bat species confer variable susceptibility to SARS-CoV entry - Yuxuan Hou; Cheng Peng; Meng Yu; Yan Li; Zhenggang Han; Fang Li; Lin-Fa Wang; Zhengli Shi (Archives of Virology, 2010)

Quantitative analysis of meso-β-scale convective cells and anvil clouds over North China - Yinjing Lin; Hongqing Wang; Lei Han; Yongguang Zheng; Yu Wang (Advances in Atmospheric Sciences, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Function of Drosophila mob2 in photoreceptor morphogenesis - Ling-Yu Liu; Cheng-Han Lin; Seng-Sheen Fan (Cell and Tissue Research, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

The effect of capillarisin on glycochenodeoxycholic acid-induced apoptosis and heme oxygenase-1 in rat primary hepatocytes - Tzung-Yan Lee; Fang-Yu Chen; Hen-Hong Chang; Han-Chieh Lin (Molecular and Cellular Biochemistry, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Effects of C-terminal amino acids truncation on enzyme properties of Aeromonas caviae D1 chitinase - Fu-Pang Lin; Hsu-Han Chuang; Yi-Hsuan Liu; Chia-Yu Hsieh; Pei-Wen Lin; Hsu-Yang Lin (Archives of Microbiology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Cadmium tolerance and accumulation by two species of Iris - Yu-Lin Han; Hai-Yan Yuan; Su-Zhen Huang; Zhi Guo; Bing Xia; Jiguang Gu (Ecotoxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

A Novel Alginate Lyase with High Activity on Acetylated Alginate of Pseudomonas aeruginosa FRD1 from Pseudomonas sp. QD03 - Lin Xiao; Feng Han; Zhao Yang; Xin-zhi Lu; Wen-gong Yu (World Journal of Microbiology and Biotechnology, 2006)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

Regional carrying capacity: case studies of Bohai Rim area - Yu Dan-lin; Mao Han-ying (Journal of Geographical Sciences, 2002)

Molecular Cloning and Sequence Analysis of the cDNAs for Pituitary Glycoprotein Hormone α Subunits from Two Species of Synbranchiformes, Monopterus albus and Ophisternon bengalense - Yu-San Han; John Yuh-Lin Yu (Fish Physiology and Biochemistry, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)